Oil level gauge

A methacrylic resin composition for oil level gauges addresses the balance of heat resistance, weather resistance, optical properties, and moldability, ensuring stability and transparency in long optical paths.

JP7608126B2Active Publication Date: 2025-01-06ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020192353
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-20
Filing Date
2020-11-19
Publication Date
2025-01-06
Estimated Expiration
2040-11-19

AI Technical Summary

Technical Problem

Existing oil level gauges face challenges in achieving a balance of heat resistance, weather resistance, optical properties, hue, and moldability, with previous resin materials being insufficient in these aspects.

Method used

A methacrylic resin composition is developed, comprising methacrylic acid ester monomer units, structural units with a ring structure in the main chain, and optional additional vinyl monomer units, with specific ratios and additives to enhance heat resistance, weather resistance, optical properties, and moldability.

Benefits of technology

The methacrylic resin composition exhibits excellent heat resistance, weather resistance, optical properties, and moldability, maintaining stability and transparency in long optical paths.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608126000001
    Figure 0007608126000001
  • Figure 0007608126000002
    Figure 0007608126000002
  • Figure 0007608126000003
    Figure 0007608126000003
Patent Text Reader

Abstract

To provide an oil level gauge containing a methacrylic resin composition which is excellent in heat resistance, weather resistance, optical characteristics, a hue and moldability.SOLUTION: The oil level gauge contains a methacrylic resin composition whose change degree (ΔYI) represented by expression (I) of a 220 mm long optical path YI value (220 mm long optical path YI value (270 seconds)) obtained by measuring a test piece prepared at a molding temperature of 280°C and cycle time of 270 seconds in injection molding according to JIS K7105 to a 220 mm long optical path YI value (220 mm long optical path YI value (45 seconds)) obtained by measuring a test piece with thickness of 3 mm, width of 20 mm and length of 220 mm prepared at a molding temperature of 280°C and cycle time of 45 seconds in injection molding according to JIS K7105 is 20 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an oil level gauge. [Background technology]

[0002] Due to their high transparency, methacrylic resins, such as polymethyl methacrylate (PMMA), have been widely used in the fields of optical materials, vehicle parts, building materials, lenses, household goods, office equipment, industrial equipment, lighting equipment, etc. In particular, in the field of optical components such as light guides, such as light guide plates and thick lenses, methacrylic resins are widely used due to the ease of molding, which is a feature of thermoplastic resins, and their outstanding transparency among thermoplastic resins.

[0003] On the other hand, oil level gauges need to have heat resistance to withstand heat generated by the internal oil, motors, etc., oil resistance to withstand oil and additives, and transparency that allows the oil level to be detected.

[0004] In view of the above circumstances, polycarbonate resins are sometimes used as materials for oil level gauges from the viewpoints of heat resistance and oil resistance. However, polycarbonate resins, especially when used for outdoor applications, are inferior in weather resistance to methacrylic resins, and therefore require the incorporation of a larger amount of ultraviolet absorbent. If the amount of ultraviolet absorbent is insufficient, the resin turns yellow, making it difficult to visually check the oil level.

[0005] For this reason, polycarbonate resins are mixed with ultraviolet absorbing agents to improve their weather resistance, but the incorporation of ultraviolet absorbing agents tends to reduce light transmittance, which makes it difficult to meet the above-mentioned requirements for long optical paths and improved brightness. In addition, polycarbonate has a high birefringence, which causes a problem of poor visibility.

[0006] In addition, for applications that do not require high transparency, i.e., high long-path transmittance, such as vehicle components, it is known to use a methacrylic copolymer resin containing a methacrylic acid monomer unit and a monomer unit having a cyclic structure (see, for example, Patent Document 1). However, the methacrylic copolymer resin disclosed in Patent Document 1 has a problem in that it does not have sufficient moldability and is not suitable for producing fine or thin optical members such as lenses. Furthermore, a technique for improving long-path optical transmittance by using a resin containing a methacrylic acid ester monomer, a maleimide monomer, and a styrene monomer has been disclosed (see, for example, Patent Document 2). According to the technology of Patent Document 2, the long light path transmittance is significantly improved, but from the viewpoint of long-term hue stability and improvement of whiteness over a long light path, there is a problem that further improvement is required. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2014-024361 A [Patent Document 2] JP 2016-210963 A Summary of the Invention [Problem to be solved by the invention]

[0008] As described above, for oil level gauges, a resin material that achieves a good balance of heat resistance, weather resistance, optical properties, color, and moldability is required. The above-mentioned conventionally proposed resin materials are still insufficient, and a higher level of properties is required.

[0009] Therefore, an object of the present invention is to provide an oil level gauge containing a methacrylic resin composition which is excellent in heat resistance, weather resistance, optical properties, color and moldability. [Means for solving the problem]

[0010] The present inventors have conducted extensive research to solve the above-mentioned problems of the conventional technology, and as a result have completed the present invention. That is, the present invention is as follows.

[0011] [1] The present invention includes a methacrylic resin composition in which the change (ΔYI) of the 220 mm long optical path YI value (220 mm long optical path YI value (45 seconds)) measured in accordance with JIS K7105 for a test piece prepared at an injection molding temperature of 280°C and a cycle time of 270 seconds relative to the 220 mm long optical path YI value (220 mm long optical path YI value (270 seconds)) measured in accordance with JIS K7105 for a test piece prepared at an injection molding temperature of 280°C and a cycle time of 270 seconds is 20 or less, The methacrylic resin composition contains a methacrylic resin containing 50 to 97 mass% of methacrylic acid ester monomer units (A), 3 to 30 mass% of structural units (B) having a ring structure in the main chain, and 0 to 20 mass% of other vinyl monomer units (C) copolymerizable with the methacrylic acid ester monomer. An oil level gauge comprising: ΔYI = {220 mm long optical path YI value (270 seconds) - 220 mm long optical path YI value (45 seconds)} / 220 mm long optical path YI value (45 seconds) (I) [2] The oil level gauge according to [1], wherein the color difference ΔE* measured according to JIS Z8730 before and after a 2040-hour exposure test using a 3 mm thick test piece using the method of JIS K7350-4 is 3 or less. [3] The oil level gauge according to [1] or [2], wherein the methacrylic resin composition contains 100 parts by mass of a methacrylic resin including a structural unit (B) having a ring structure in its main chain, and 0.001 to 0.2 parts by mass of a compound (D) represented by the following general formula (1) or (2): [ka] In formula (1), R represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 12 carbon atoms, or a 6 R' represents an aliphatic hydrocarbon group having 1 to 12 carbon atoms or an aromatic hydrocarbon group having 6 to 18 carbon atoms. R' represents an aliphatic hydrocarbon group having 1 to 12 carbon atoms or an aromatic hydrocarbon group having 6 to 18 carbon atoms. R' represents an aliphatic hydrocarbon group having 1 to 12 carbon atoms and ... [ka] In formula (2), R, R', and R'' each independently represent a hydrogen atom, an aliphatic hydrocarbon group having 1 to 12 carbon atoms, or 6 The aliphatic hydrocarbon group and aromatic hydrocarbon group of R, R', and R'' may each have a sulfur atom, a nitrogen atom, an oxygen atom, or a phosphorus atom on a carbon atom. R' and R'' may be bonded to each other to form a ring. [4] The oil level gauge according to [3], wherein a ratio ((B) / (D)) of a content of the structural unit (B) having a ring structure in the main chain in the methacrylic resin composition to a content of the component (D) in the methacrylic resin composition is 25 or more and 1,000 or less. [5] The oil level gauge according to [2] or [3], wherein the methacrylic resin composition has a weight average molecular weight of 65,000 to 300,000 as measured by gel permeation chromatography (GPC). [6] The oil level gauge according to any one of [1] to [5], wherein the structural unit (B) having a ring structure in the main chain includes at least one structural unit selected from the group consisting of a maleimide-based structural unit (B-1), a glutaric anhydride-based structural unit (B-2), a glutarimide-based structural unit (B-3), a lactone ring structural unit (B-4), and an acid anhydride structural unit (B-5). [7] The oil level gauge according to any one of [1] to [6], having a thickness of 0.01 to 30 mm. Effect of the Invention

[0012] According to the present invention, it is possible to provide an oil level gauge containing a methacrylic resin composition which is excellent in heat resistance, weather resistance, optical properties, color and moldability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Below, a form for implementing the present invention (hereinafter referred to as the "present embodiment") will be described in detail, but the present invention is not limited to the following description and can be implemented in various modified forms within the scope of its gist. In the following description, a structural unit constituting the polymer constituting the methacrylic resin contained in the methacrylic resin composition used in the present embodiment is referred to as a "monomer unit" and / or a "structural unit" containing a plurality of the "monomer units". Furthermore, the constituent material of such a "monomer unit" may be referred to simply as "monomer" without the "unit."

[0014] (Methacrylic resin composition) The methacrylic resin composition used in the present embodiment has a change rate (ΔYI) of 20 or less between the 220 mm long optical path YI value (220 mm long optical path YI value (45 seconds)) measured in accordance with JIS K7105 for a test piece prepared at an injection molding temperature of 280°C and a cycle time of 270 seconds, and the 220 mm long optical path YI value (220 mm long optical path YI value (270 seconds)) measured in accordance with JIS K7105 for a test piece prepared at an injection molding temperature of 280°C and a cycle time of 270 seconds. ΔYI = {220 mm long optical path YI value (270 seconds) - 220 mm long optical path YI value (45 seconds)} / 220 mm long optical path YI value (45 seconds) (I)

[0015] The methacrylic resin composition of the present embodiment may contain a methacrylic resin, a compound (D), other components, and the like. The methacrylic resin composition of the present embodiment preferably contains 80% by mass or more of the methacrylic resin relative to 100% by mass of the methacrylic resin composition, more preferably 85% by mass or more, even more preferably 90% by mass or more, and even more preferably 95% by mass or more. By setting the content of the methacrylic resin to the above-mentioned preferred amount, it is possible to improve the heat resistance, weather resistance, optical properties, hue, and moldability required for the oil level gauge.

[0016] (Methacrylic resin) The methacrylic resin used in the methacrylic resin composition used in the present embodiment is not particularly limited in its composition, but may contain 50 to 97 mass% of methacrylic acid ester monomer units (A), 3 to 30 mass% of structural units (B) having a ring structure in the main chain, and 0 to 20 mass% of other vinyl monomer units (C) copolymerizable with the methacrylic acid ester monomers.

[0017] <Methacrylic acid ester monomer unit (A)> As the methacrylic acid ester monomer unit (A) (hereinafter, sometimes referred to as (A) monomer unit) constituting the methacrylic resin, a monomer unit represented by the following general formula (A) is suitably used.

[0018] [ka]

[0019] In the general formula (a), R 1 R represents a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted with a hydroxyl group. 1 is preferably a methyl group. R 2 R represents a group having 1 to 12 carbon atoms, preferably a hydrocarbon group having 1 to 12 carbon atoms, which may be substituted with a hydroxyl group. 2is preferably a group having 1 to 8 carbon atoms.

[0020] The monomer constituting the methacrylic acid ester monomer unit (A) represented by the above general formula (A) is not particularly limited, but it is preferable to use a methacrylic acid ester monomer represented by the following general formula (B).

[0021] [ka]

[0022] In the above general formula (b), R 1 R represents a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted with a hydroxyl group. 1 is preferably a methyl group. R 2 R represents a group having 1 to 12 carbon atoms, preferably a hydrocarbon group having 1 to 12 carbon atoms, which may be substituted with a hydroxyl group. 2 is preferably a group having 1 to 8 carbon atoms.

[0023] Examples of methacrylic acid ester monomers include, but are not limited to, butyl methacrylate, ethyl methacrylate, methyl methacrylate, propyl methacrylate, isopropyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, 2-ethylhexyl methacrylate, t-butylcyclohexyl methacrylate, benzyl methacrylate, and 2,2,2-trifluoroethyl methacrylate. From the viewpoints of heat resistance, ease of handling, and optical properties, the methacrylic acid ester monomer is preferably methyl methacrylate, ethyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, or benzyl methacrylate, and from the viewpoint of availability, etc., methyl methacrylate is preferred. The methacrylic acid ester monomers may be used alone or in combination of two or more kinds.

[0024] The methacrylic acid ester monomer unit (A) of the methacrylic resin must be contained in an amount of 50% by mass or more and 97% by mass or less in the methacrylic resin in order to provide sufficient heat resistance and good color to the methacrylic resin composition used in this embodiment and the oil level gauge of this embodiment by the structural unit (B) having a ring structure in the main chain described later. The content is preferably 55% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, and even more preferably 90% by mass or more. Furthermore, when it is necessary to impart particularly high heat resistance, the content of the methacrylic acid ester monomer unit (A) in the methacrylic resin is preferably 96 mass % or less, and more preferably 95 mass % or less.

[0025] <Structural unit (B) having a ring structure in the main chain> The structural unit (B) having a ring structure in the main chain constituting the methacrylic resin (hereinafter, may be referred to as a (B) structural unit) preferably contains at least one structural unit selected from the group consisting of a maleimide structural unit (B-1), a glutaric anhydride structural unit (B-2), a glutarimide structural unit (B-3), a lactone ring structural unit (B-4), and an anhydride oxide (B-5) from the viewpoint of heat resistance. The structural unit (B) having a ring structure in the main chain may be used alone or in combination of two or more kinds.

[0026] [Maleimide structural unit (B-1)] As the maleimide structural unit (B-1) constituting the methacrylic resin, a structural unit represented by the following general formula (III) is preferably used.

[0027] [ka]

[0028] In the above general formula (III), R 1represents any one selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, a cycloalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, and an aryl group having 6 to 12 carbon atoms, and the alkyl group, alkoxy group, cycloalkyl group, and aryl group may have a substituent on a carbon atom.

[0029] Examples of monomers for forming the maleimide structural unit (B-1) include, but are not limited to, maleimide; N-alkyl group-substituted maleimides such as N-methylmaleimide, N-ethylmaleimide, and N-cyclohexylmaleimide; and N-aryl group-substituted maleimides such as N-phenylmaleimide, N-methylphenylmaleimide, N-ethylphenylmaleimide, N-butylphenylmaleimide, N-dimethylphenylmaleimide, N-hydroxyphenylmaleimide, N-methoxyphenylmaleimide, N-(o-chlorophenyl)maleimide, N-(m-chlorophenyl)maleimide, and N-(p-chlorophenyl)maleimide. From the viewpoints of imparting heat resistance and moist heat resistance, preferred examples of the monomer for forming the maleimide structural unit (B-1) include N-cyclohexylmaleimide, N-phenylmaleimide, N-methylphenylmaleimide, N-(o-chlorophenyl)maleimide, N-(m-chlorophenyl)maleimide, and N-(p-chlorophenyl)maleimide. From the viewpoints of availability and imparting heat resistance, more preferred examples include N-cyclohexylmaleimide and N-phenylmaleimide, and even more preferred examples include N-phenylmaleimide. The maleimide structural unit (B-1) may be used alone or in combination of two or more kinds.

[0030] [Glutaric anhydride structural unit (B-2)] The glutaric anhydride structural unit (B-2) constituting the methacrylic resin may be formed after polymerization of the methacrylic resin. As the (B-2) structural unit, a structural unit represented by the following general formula (IV) is preferably used.

[0031] [ka]

[0032] In the above general formula (IV), R 1 and R 2 each independently represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted with a hydroxyl group. The glutaric anhydride structural unit (B-2) may be used alone or in combination of two or more kinds.

[0033] The method for forming the glutaric anhydride structural unit (B-2) is not particularly limited, and examples thereof include a method in which a monomer having a structure represented by the following general formula (e) is copolymerized with a monomer constituting the above-mentioned methacrylic acid ester monomer unit (A), and then cyclized by heat treatment in the presence / absence of a catalyst.

[0034] [ka]

[0035] In the general formula (e), R 1 represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted with a hydroxyl group. R 2 represents a hydrogen atom or a t-butyl group. Furthermore, as long as the effects of the present invention can be exhibited, the monomer having the structure represented by the general formula (e) may remain unreacted in the methacrylic resin.

[0036] [Glutarimide structural unit (B-3)] The glutarimide structural unit (B-3) constituting the methacrylic resin may be formed after the resin polymerization. As the (B-3) structural unit, a structural unit represented by the following general formula (f) is preferably used.

[0037] [ka]

[0038] In the above general formula (F), R 1 and R 2 each independently represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted with a hydroxyl group. Also, R 3 represents any one selected from the group consisting of a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and a substituted or unsubstituted aryl group having 6 to 18 carbon atoms. Particularly preferably, R 1 , R 2 , and R 3 are all methyl groups. The glutarimide structural unit (B-3) may be used alone or in combination of two or more kinds.

[0039] The content of the glutarimide structural unit (B-3) is not particularly limited and can be appropriately determined taking into consideration heat resistance, moldability, optical properties, and the like. The content of the glutarimide structural unit (B-3) is preferably from 1 to 50% by mass, more preferably from 3 to 30% by mass, and further preferably from 3 to 20% by mass, based on 100% by mass of the methacrylic resin. The content of the glutarimide structural unit (B-3) can be calculated, for example, by the method described in

[0136] to

[0137] of WO 2015 / 098096.

[0040] The acid value of the resin containing the glutarimide structural unit (B-3) is preferably 0.50 mmol / g or less, more preferably 0.45 mmol / g or less, in consideration of the balance of the physical properties, moldability, color tone, and the like of the resin. The acid value can be calculated, for example, by the titration method described in JP-A-2005-23272.

[0041] The glutarimide structural unit (B-3) can be obtained by a known method, such as a method of copolymerizing a methacrylic acid ester and / or methacrylic acid, followed by reacting ammonia or an amine with urea or unsubstituted urea at high temperature, a method of reacting a methyl methacrylate-methacrylic acid-styrene copolymer or a methyl methacrylate-styrene copolymer with ammonia or an amine, or a method of reacting polymethacrylic anhydride with ammonia or an amine. Specifically, there may be mentioned the method described in US Pat. No. 4,246,374 to RMKopchik. The glutarimide structural unit (B-3) can also be formed by imidizing an acid anhydride such as maleic anhydride, a half ester of the acid anhydride with a linear or branched alcohol having 1 to 20 carbon atoms, or an α,β-ethylenically unsaturated carboxylic acid.

[0042] Furthermore, another preferred method for forming the glutarimide structural unit (B-3) includes a method in which a (meth)acrylic acid ester and, if necessary, an aromatic vinyl monomer or other vinyl monomers are polymerized, followed by an imidization reaction to obtain a resin containing the glutarimide structural unit (B-3). In the imidization reaction step, an imidization agent may be used, and a ring-closing promoter may be added as necessary. The imidizing agent may be ammonia or a primary amine, and examples of the primary amine that may be used include methylamine, ethylamine, n-propylamine, and cyclohexylamine. The method for carrying out the imidization reaction is not particularly limited, and a conventionally known method can be used, for example, a method using an extruder, a horizontal twin-screw reaction apparatus, or a batch reaction tank. The extruder is not particularly limited, and a single-screw extruder, a twin-screw extruder, or a multi-screw extruder can be preferably used. More preferably, a tandem-type reactive extruder in which two twin-screw extruders are arranged in series can be used.

[0043] In addition, in producing the methacrylic resin containing the glutarimide structural unit (B-3), an esterification step of treating with an esterifying agent can be included in addition to the imidization reaction step. By including the esterification step, carboxyl groups contained in the methacrylic resin that are by-produced during the imidization step can be converted into ester groups, and the acid value of the resin can be adjusted to a desired range. The esterification agent is not particularly limited as long as it can exhibit the effects of the present invention, but preferably dimethyl carbonate or trimethyl acetate can be used. The amount of the esterification agent used is not particularly limited, but is preferably 0 to 12 parts by mass relative to 100 parts by mass of the methacrylic resin. In addition to the esterification agent, an aliphatic tertiary amine such as trimethylamine, triethylamine, or tributylamine can also be used in combination as a catalyst.

[0044] [Lactone ring structural unit (B-4)] The lactone ring structural unit (B-4) constituting the methacrylic resin may be formed after polymerization of the methacrylic resin. As the (B-4) structural unit, a structural unit represented by the following general formula (G) is preferably used.

[0045] [ka]

[0046] In the above general formula (G), R 1 , R 2 , and R 3 each independently represents a hydrogen atom or an organic group having 1 to 20 carbon atoms. The organic group may contain an oxygen atom. The lactone ring structural unit (B-4) may be used alone or in combination of two or more kinds.

[0047] The method for producing a polymer containing a lactone ring structural unit (B-4) is not particularly limited, but examples thereof include a method in which a monomer having a hydroxyl group in a side chain, specifically a monomer having a structure represented by the following general formula (h) (e.g., 2-(hydroxymethyl)methyl acrylate) is copolymerized with a monomer having an ester group, such as the above-mentioned methacrylic acid ester monomer (A), and the resulting copolymer is then heat-treated in the presence / absence of a specific catalyst to introduce a lactone ring structure into the polymer.

[0048] [ka]

[0049] In the above general formula (H), R 1 represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted with a hydroxyl group. R 2 represents a group having 1 to 12 carbon atoms, preferably a hydrocarbon group having 1 to 12 carbon atoms, which may be substituted with a hydroxyl group. Particularly preferably, R 1 is a hydrogen atom, and R 2 is a methyl group. Furthermore, as long as the effects of the present invention can be exhibited, the monomer having the structure represented by the general formula (h) may remain unreacted in the methacrylic resin.

[0050] [Acid anhydride structural unit (B-5)] The acid anhydride structural unit (B-5) constituting the methacrylic resin can be formed by suitably using, for example, an acid anhydride such as maleic anhydride, a half ester of the acid anhydride with a linear or branched alcohol having 1 to 20 carbon atoms, or an α,β-ethylenically unsaturated carboxylic acid.

[0051] The structural unit (B) having a ring structure in the main chain contained in the above-mentioned methacrylic resin preferably contains at least one structural unit selected from the group consisting of maleimide-based structural units (B-1) and glutarimide-based structural units (B-3) in terms of thermal stability and moldability, and more preferably contains a maleimide-based structural unit (B-1). Among the maleimide structural units (B-1), in consideration of ease of availability, N-cyclohexylmaleimide structural units and / or N-aryl-substituted maleimide structural units are preferred, and in terms of the hue of the molded product, N-cyclohexylmaleimide structural units are more preferred.

[0052] The content of the structural unit (B) having a ring structure in the main chain in the methacrylic resin is 3 mass% or more, preferably 4 mass% or more, and more preferably 5 mass% or more, from the viewpoint of imparting heat resistance and thermal stability to the methacrylic resin composition used in the present embodiment. From the viewpoint of maintaining a good balance between the strength and fluidity required for a molded body, the content of the structural unit (B) having a ring structure in the main chain in the methacrylic resin is 30 mass% or less, preferably 25 mass% or less, more preferably 20 mass% or less, even more preferably 14 mass% or less, and even more preferably 10 mass% or less.

[0053] In particular, when a maleimide-based structural unit (B-1) is used as the structural unit (B) having a ring structure in the main chain, the content of the maleimide-based structural unit (B-1) is preferably less than 50 mass%, more preferably less than 40 mass%, even more preferably less than 35 mass%, still more preferably 1 to 30 mass%, and even more preferably 2 to 20 mass%, when the total amount of the methacrylic acid ester monomer unit (A) and the structural unit (B) having a ring structure in the main chain is taken as 100 mass%, from the viewpoints of heat resistance and thermal stability.

[0054] <Other vinyl monomer units copolymerizable with methacrylic acid ester monomers (C)> In the methacrylic resin, from the viewpoint of obtaining a resin superior in weather resistance, fluidity, chemical resistance, thermal stability, etc., and imparting other properties, it is preferable to copolymerize other vinyl monomer units. For example, there may be mentioned an acrylic acid ester monomer unit (C-1) or a vinyl cyanide monomer unit (C-2).

[0055] [Acrylic acid ester monomer unit (C-1)] The monomer used to form the acrylic acid ester monomer unit (C-1) constituting the methacrylic resin is not particularly limited, but is preferably an acrylic acid ester monomer represented by the following general formula (i):

[0056] [ka]

[0057] In the above general formula (i), R 1 represents a hydrogen atom or an alkoxy group having 1 to 12 carbon atoms; R 2 represents an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 1 to 18 carbon atoms, or an aryl group having 1 to 18 carbon atoms.

[0058] As a monomer for forming the acrylic ester monomer unit (C-1), from the viewpoint of improving weather resistance, heat resistance, fluidity, and thermal stability in the methacrylic resin used in this embodiment, preferred are methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, sec-butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, phenyl acrylate, and the like, more preferred are methyl acrylate, ethyl acrylate, and n-butyl acrylate, and from the viewpoint of easy availability, methyl acrylate and ethyl acrylate are even more preferred. The acrylic acid ester monomer unit (C-1) may be used alone or in combination of two or more kinds. When the acrylic acid ester monomer unit (C-1) is used, its content is preferably 5% by mass or less, and more preferably 3% by mass or less, when the total amount of the (A) monomer unit and the (B) structural unit is taken as 100% by mass, from the viewpoints of heat resistance and thermal stability.

[0059] [Cyanide vinyl monomer unit (C-2)] In the methacrylic resin, the monomer unit (C) is preferably a vinyl cyanide monomer unit (C-2) from the viewpoints of easy availability and of obtaining a resin having even more excellent chemical resistance. The monomer used to form the vinyl cyanide monomer unit (C-2) constituting the methacrylic resin includes, but is not limited to, acrylonitrile, methacrylonitrile, vinylidene cyanide, etc., and among them, acrylonitrile is preferred from the viewpoints of availability and chemical resistance. The vinyl cyanide monomer unit (C-2) may be used alone or in combination of two or more kinds. When the vinyl cyanide monomer unit (C-2) is used, its content is preferably 15% by mass or less, more preferably 12% by mass or less, and even more preferably 10% by mass or less, when the total amount of the monomer unit (A) and the structural unit (B) is taken as 100% by mass, from the viewpoint of maintaining solvent resistance and heat resistance.

[0060] [Monomer unit (C-3) other than (C-1) to (C-2)] The monomer used to form the monomer unit (C-3) other than (C-1) to (C-2) constituting the methacrylic resin is not limited to the following, but examples thereof include amides such as styrene, acrylamide, and methacrylamide; ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and other ethylene glycol or oligomers thereof, both terminal hydroxyl groups of which are esterified with acrylic acid or methacrylic acid; neopentyl glycol di(meth)acrylate, di(meth)acrylate, and other two alcohol hydroxyl groups of which are esterified with acrylic acid or methacrylic acid; trimethylolpropane, pentaerythritol, and other polyhydric alcohol derivatives esterified with acrylic acid or methacrylic acid; and polyfunctional monomers such as divinylbenzene.

[0061] Among the monomers used to form the monomer unit (C) described above, at least one selected from the group consisting of methyl acrylate, ethyl acrylate, and acrylonitrile is preferred from the viewpoint of availability, and methyl acrylate (C) is preferred from the viewpoint of maintaining transmittance and hue in a long optical path of 100 mm or more.

[0062] The content of the other vinyl monomer units (C) copolymerizable with the methacrylic acid ester monomer is 0 to 20 mass%, preferably 0 to 18 mass%, and more preferably 0 to 15 mass%, based on 100 mass% of the methacrylic resin, from the viewpoint of enhancing the effect of imparting heat resistance by the structural units (B). In particular, when a styrene monomer unit is used as the (C) monomer unit, the content of the styrene monomer unit is preferably 0 to 6 mass% or less, more preferably 0 to 5 mass% or less, and even more preferably 0 to 3 mass% or less, based on 100 mass% of the methacrylic resin, from the viewpoint of improving weather resistance. In particular, when a crosslinkable polyfunctional (meth)acrylate having a plurality of reactive double bonds is used as the (C) monomer unit, the content of the (C) monomer unit is preferably 0.5 mass % or less, more preferably 0.3 mass % or less, and even more preferably 0.2 mass % or less, from the viewpoint of fluidity.

[0063] (Compound (D)) The compound (D) that can be contained in the methacrylic resin composition of the present embodiment is represented by the following general formula (1) or (2).

[0064] [ka] (1)

[0065] Here, R is a hydrogen atom, an aliphatic hydrocarbon group having 1 to 12 carbon atoms, or 6 It represents an aromatic hydrocarbon group of from 1 to 12. The aliphatic hydrocarbon group and aromatic hydrocarbon group of R may each have a sulfur atom, a nitrogen atom, an oxygen atom or a phosphorus atom on a carbon atom. Furthermore, R' represents an aliphatic hydrocarbon group having 1 to 12 carbon atoms or an aromatic hydrocarbon group having 6 to 18 carbon atoms. The aliphatic hydrocarbon group and aromatic hydrocarbon group of R' may each have a sulfur atom, a nitrogen atom, an oxygen atom or a phosphorus atom on a carbon atom.

[0066] [ka] (2)

[0067] Here, R, R', and R'' each independently represent a hydrogen atom, an aliphatic hydrocarbon group having 1 to 12 carbon atoms, or 6 The aliphatic hydrocarbon group and aromatic hydrocarbon group of R, R', and R'' may each have a sulfur atom, a nitrogen atom, an oxygen atom, or a phosphorus atom on a carbon atom. R' and R'' may be bonded to each other to form a ring.

[0068] From the viewpoint of suppressing the degree of change in the YI value during long-term residence, the compound (D) preferably has a succinimide skeleton of the above formula (1), and more preferably has a 3-hydroxysuccinimide skeleton in which R in the above formula (1) is a hydrogen atom.

[0069] From the viewpoint of minimizing the degree of change in the YI value during molding when repeatedly exposed to high temperatures for long periods of time, the content of compound (D) is preferably 0.001 part by mass or more relative to 100 parts by mass of the methacrylic resin, more preferably 0.005 part by mass or more, even more preferably 0.01 part by mass or more, still more preferably 0.015 parts by mass or more, still more preferably 0.02 part by mass or more, and particularly preferably 0.03 part by mass or more. Furthermore, from the viewpoint of maintaining high transmittance over a long optical path and high whiteness, the content is preferably 0.2 parts by mass or less, more preferably 0.15% by mass or less, even more preferably 0.12% by mass or less, even more preferably 0.11% by mass or less, and even more preferably 0.1% by mass or less. By including a certain amount of compound (D), thermal decomposition of the methacrylic resin is suppressed when it is placed in a high-temperature environment, and the effects of reducing yellowing over a long optical path and improving transmittance stability are obtained.

[0070] In this embodiment, the mass ratio of the compound (D) to the structural unit (B) having a ring structure in the main chain in the methacrylic resin composition is in the range of 25≦(B) / (D)≦1000 from the viewpoints of obtaining the effects of stability of YI during continuous molding, reduction of yellowing over a long optical path, and improvement of transmittance stability, as well as reduction of silver streaks and the like during molding processing. From the viewpoint of reducing the yellowing degree dependency of the methacrylic resin composition on the thickness from 3 mm to 220 mm, that is, the change in the YI value between each thickness when the YI value is measured for a molded piece having a predetermined thickness between 3 mm and 220 mm, the (B) / (D) is preferably 800 or less, more preferably 700 or less, even more preferably 600 or less, and even more preferably 500 or less. From the viewpoint of the heat resistance of the methacrylic resin composition, the (B) / (D) is preferably 30 or more, more preferably 45 or more, and even more preferably 50 or more.

[0071] The characteristics of methacrylic resins are described below.

[0072] <Weight average molecular weight, molecular weight distribution> The weight average molecular weight (Mw) of the methacrylic resin of this embodiment is 65,000 to 300,000 from the viewpoint of obtaining a methacrylic resin having even more excellent mechanical strength, solvent resistance, and fluidity. By setting the weight average molecular weight of the methacrylic resin within the above range, the methacrylic resin and the methacrylic resin composition used in the present embodiment will have excellent mechanical strength, such as Charpy impact strength, and flowability. From the viewpoint of maintaining mechanical strength, the weight average molecular weight is preferably 65,000 or more, more preferably 70,000 or more, even more preferably 80,000 or more, and still more preferably 100,000 or more. In addition, from the viewpoints of ensuring flowability during molding, reducing distortion during molding, and imparting long path transmittance, the weight average molecular weight is preferably 250,000 or less, more preferably 200,000 or less, even more preferably 150,000 or less, even more preferably 130,000 or less, and still more preferably 120,000 or less. From the viewpoint of the balance between fluidity, mechanical strength, and solvent resistance, the molecular weight distribution (weight average molecular weight (Mw) / number average molecular weight (Mn)) of the methacrylic resin is preferably 1.5 to 5. It is more preferably 1.5 to 4.5, even more preferably 1.6 to 4, even more preferably 1.6 to 3, and even more preferably 1.6 to 2.5. The weight average molecular weight (Mw) and number average molecular weight (Mn) can be measured by gel permeation chromatography (GPC). In detail, a calibration curve is prepared from the elution time and the weight average molecular weight using a standard methacrylic resin whose monodisperse weight average molecular weight, number average molecular weight, and peak molecular weight are known and available as a reagent, and an analytical gel column that elutes high molecular weight components first. Next, the weight average molecular weight and number average molecular weight of the methacrylic resin sample to be measured can be obtained from the obtained calibration curve. Specifically, it can be measured by the method described in the Examples below.

[0073] (Methacrylic resin manufacturing method) The method for producing the methacrylic resin is not particularly limited as long as the above-mentioned methacrylic resin can be obtained.

[0074] The methacrylic resin can be produced by bulk polymerization, solution polymerization, suspension polymerization, precipitation polymerization, or emulsion polymerization using each monomer for forming the methacrylic acid ester monomer unit (A), the structural unit (B) having a ring structure in the main chain, and, if necessary, the other vinyl monomer unit (C) copolymerizable with the above-mentioned methacrylic acid ester monomer. Preferably, bulk polymerization, solution polymerization, and suspension polymerization are used, more preferably solution polymerization and suspension polymerization, and further preferably suspension polymerization is used. The methacrylic resin may be produced in a continuous manner or in a batch manner. In the method for producing the methacrylic resin, it is preferable to polymerize the monomers by radical polymerization.

[0075] In the polymerization reaction of the methacrylic resin, a polymerization initiator may be used. The polymerization initiator may be any one that decomposes at the polymerization temperature to generate active radicals, but it is necessary to achieve the required polymerization conversion within the range of the residence time, and a polymerization initiator having a half-life of 0.6 to 60 minutes, preferably 1 to 30 minutes at the polymerization temperature is selected. However, even with respect to a polymerization initiator having a half-life of more than 60 minutes at the polymerization temperature, it can be used as a polymerization initiator that generates an amount of active radicals suitable for this embodiment by adding a predetermined amount at once or over a period of about 10 minutes. In this case, in order to achieve the required polymerization conversion, a polymerization initiator having a half-life of 60 to 1800 minutes, preferably 260 to 900 minutes at the polymerization temperature is selected. A polymerization initiator to be suitably used can be appropriately selected in consideration of the polymerization temperature and polymerization time. For example, initiators described in "Organic Peroxides" 13th Edition published by Nippon Oil & Fats Co., Ltd., technical data published by Atochem Yoshitomi Co., Ltd., and "Azo Polymerization Initiators" published by Wako Pure Chemical Industries, Ltd. can be suitably used. The half-life can be easily determined from various constants described therein.

[0076] In the case of radical polymerization, the polymerization initiator is not limited to the following, but examples thereof include di-t-butyl peroxide, lauroyl peroxide, stearyl peroxide, benzoyl peroxide, t-butyl peroxy neodecane, t-butyl peroxy pivalate, dilauroyl peroxide, dicumyl peroxide, t-butylperoxy-2-ethylhexanoate, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane (e.g., For example, Perhexa (registered trademark) C), acetyl peroxide, capryl peroxide, 2,4-dichlorobenzoyl peroxide, isobutyl peroxide, acetylcyclohexylsulfonyl peroxide, t-butyl peroxybiparatate, t-butyl peroxy-2-ethylhexanoate, iso-propyl peroxydicarbonate, iso-butyl peroxydicarbonate, sec-butyl peroxydicarbonate, n-butyl peroxydicarbonate, 2-ethylhexyl peroxydicarbonate, bis(4-t- butylcyclohexyl)peroxydicarbonate, t-amylperoxy-2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxyethylhexanoate, 1,1,2-trimethylpropylperoxy-2-ethylhexanoate, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane (e.g., Perhexa® 25B), t-butylperoxyisopropyl monocarbonate, t-amylperoxyisopropyl monocarbonate, 1,1,3,3-tetramethylbutylperoxyisopropyl monocarbonate Organic peroxides such as 1,1,2-trimethylpropylperoxyisopropyl monocarbonate, 1,1,3,3-tetramethylbutylperoxyisononate, 1,1,2-trimethylpropylperoxy-isononate, and t-butylperoxybenzoate, as well as azobisisobutyronitrile, azobisisovaleronitrile, azobisdimethylvaleronitrile, azobiscyclohexanenitrile, 1,1-azobis(1-cyclohexanecarbonitrile), 2,2'-azobis-4-methoxy-2,4-azobisisobutyronitrile, 2,Examples of typical radical polymerization initiators include azo compounds such as 2'-azobis-2,4-dimethylvaleronitrile, 2,2'-azobis-2-methylbutyronitrile, 1,1'-azobis(1-acetoxy-1-phenylethane), dimethyl-2,2'-azobisisobutyrate, and 4,4'-azobis-4-cyanovaleric acid.

[0077] The above-mentioned radical polymerization initiators may be used as redox initiators in combination with an appropriate reducing agent. These polymerization initiators can be used alone or in combination of two or more.

[0078] The polymerization initiator may be added in an amount necessary to obtain a desired polymerization rate in a polymerization reactor. In a polymerization reaction, the degree of polymerization can be increased by increasing the amount of polymerization initiator supplied. However, using a large amount of polymerization initiator tends to decrease the overall molecular weight and increases the amount of heat generated during polymerization, which may result in a decrease in polymerization stability due to overheating. From the viewpoint of making it easier to obtain a desired molecular weight and ensuring polymerization stability, the polymerization initiator is used in an amount of preferably 0 to 1 part by mass, more preferably 0.001 to 0.8 parts by mass, and even more preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the total amount of all monomers used. The amount of the polymerization initiator to be added can be appropriately selected taking into consideration the temperature at which the polymerization is carried out and the half-life of the initiator.

[0079] In the polymerization reaction of the methacrylic resin, a chain transfer agent, an iniferter, or the like can be optionally used as a molecular weight regulator. In the process for producing the methacrylic resin, the molecular weight of the polymer produced can be controlled within a range that does not impair the object of the present invention. Examples of chain transfer agents and iniferters include, but are not limited to, alkyl mercaptans, dimethylacetamide, dimethylformamide, triethylamine, and other chain transfer agents; dithiocarbamates, triphenylmethylazobenzene, tetraphenylethane derivatives, and other iniferters; and the like, which can be used to control the molecular weight. Furthermore, the molecular weight can be controlled by adjusting the amount of these chain transfer agents and iniferters added.

[0080] When these chain transfer agents or iniferters are used, alkyl mercaptans are preferably used from the viewpoints of handling and stability. Examples of such alkyl mercaptans include, but are not limited to, n-butyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, n-tetradecyl mercaptan, n-octadecyl mercaptan, 2-ethylhexyl thioglycolate, ethylene glycol dithioglycolate, trimethylolpropane tris(thioglycolate), pentaerythritol tetrakis(thioglycolate), and the like. These molecular weight modifiers can be added as appropriate depending on the required molecular weight, but are generally used in an amount of 0.001 to 3 parts by mass per 100 parts by mass of the total amount of all monomers used.

[0081] Other methods for controlling the molecular weight include changing the polymerization method, adjusting the amount of the polymerization initiator, and changing the polymerization temperature. These molecular weight control methods may be used alone or in combination of two or more kinds.

[0082] In the methacrylic resin, a chain transfer agent (molecular weight regulator) may be used for the purpose of improving the thermal stability of the polymer in addition to adjusting the molecular weight. The type and method of use of the chain transfer agent to be used are not limited as long as the effects of the present invention can be exhibited.

[0083] <Production method using suspension polymerization method> When the methacrylic resin is produced by suspension polymerization such as organic suspension polymerization or inorganic suspension polymerization, a particulate methacrylic resin is produced through a polymerization step, a washing step, a dehydration step, and a drying step using a stirring device described later. Usually, an aqueous suspension polymerization method using water as a medium is preferably used.

[0084] [Polymerization process] In the polymerization step, a predetermined stirring device is used, and the raw material monomers, a suspending agent, and optionally a polymerization initiator and other additives are appropriately supplied to the stirring device to carry out polymerization, thereby obtaining a slurry of a methacrylic resin. Examples of the stirring device used in the polymerization step for obtaining a methacrylic resin by suspension polymerization include known stirring devices such as a stirring device having a stirring blade such as an inclined paddle blade, a flat paddle blade, a propeller blade, an anchor blade, a Pfaudler blade (swept back blade), a turbine blade, a Blue Margin blade, a Max Blend blade, a Full Zone blade, a ribbon blade, a Super Mix blade, an Intermig blade, a special blade, or an axial flow blade inside, a stirring device having a shovel blade inside, a stirring device having a chopper blade inside, and a stirring device having a rotating disk such as a disk type, a notched disk type, or a screw type inside. The stirring speed during polymerization depends on the type of stirring device used, the stirring efficiency of the stirring blades, the volume of the polymerization tank, etc., but is preferably about 1 to 500 revolutions / minute in consideration of the ability to obtain an appropriate particle size, the ability to reduce the content of components having a particle size of less than 0.15 mm, polymerization stability, etc.

[0085] The temperature when adding the raw material mixture of the methacrylic resin may be within a range in which the effects of the present invention can be exhibited, and is preferably 0°C or higher and below the boiling point of the raw material used. If the temperature is high, the raw materials tend to volatilize during addition, which changes the composition of the copolymer constituting the resulting methacrylic resin, and if the temperature is low and below 0°C, it takes time to increase the temperature after adding the raw materials, so it is preferable to add the raw material mixture at a certain temperature. Specifically, the temperature is preferably 0°C or higher and 85°C or lower, more preferably 10°C or higher and 85°C or lower, even more preferably 30°C or higher and 85°C or lower, even more preferably 50°C or higher and 80°C or lower, and even more preferably 60°C or higher and 80°C or lower. In consideration of productivity and the amount of aggregates produced, the temperature in the suspension polymerization step is preferably 40° C. or higher and 90° C. or lower, more preferably 50° C. or higher and 85° C. or lower, even more preferably 60° C. or higher and 85° C. or lower, and even more preferably 65° C. or higher and 83° C. or lower.

[0086] The polymerization time in the suspension polymerization is preferably 20 minutes or more and 240 minutes or less, more preferably 30 minutes or more and 210 minutes or less, even more preferably 45 minutes or more and 180 minutes or less, still more preferably 60 minutes or more and 180 minutes or less, and still more preferably 90 minutes or more and 150 minutes or less, from the viewpoints of effectively suppressing heat generation during polymerization and reducing the generation of aggregates and residual monomers, which will be described later.

[0087] From the viewpoint of reducing the amount of residual monomers, it is preferable to raise the temperature to a temperature higher than the polymerization temperature after the polymerization step and maintain the temperature for a certain period of time. The temperature at which the mixture is maintained is preferably higher than the polymerization temperature because the degree of polymerization can be increased. When the temperature is higher, the temperature is preferably increased by 5° C. or more from the polymerization temperature. When the temperature is increased, it is preferably equal to or lower than the glass transition temperature of the resulting methacrylic resin in order to prevent aggregation of the resulting polymer. Specifically, it is 120°C or less, preferably 100°C or less, more preferably 80°C or more and 100°C or less, even more preferably 85°C or more and 100°C or less, even more preferably 88°C or more and 100°C or less, and still more preferably 90°C or more and 100°C or less. By carrying out the polymerization at the above-mentioned polymerization temperature and holding time, it is possible to produce polymer particles having a small angle of repose after the drying step described below. Taking into consideration the effect of reducing residual monomers, the time for which the temperature is maintained after heating is preferably from 15 minutes to 360 minutes, more preferably from 30 minutes to 240 minutes, even more preferably from 30 minutes to 180 minutes, still more preferably from 30 minutes to 150 minutes, and even more preferably from 30 minutes to 120 minutes.

[0088] In order to reduce the amount of residual monomers, an organic solvent may be used during polymerization within a range that does not affect polymerization stability. Suitable organic solvents are those that can dissolve the resulting resin, and aromatic hydrocarbon solvents such as xylene, toluene, and ethylbenzene are suitable. When used, the amount used is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 8 parts by mass or less, and even more preferably 6 parts by mass or less, based on 100 parts by mass of the total amount of monomers used.

[0089] [Cleaning process] The methacrylic resin slurry obtained through the above-mentioned polymerization step is preferably subjected to an operation such as acid washing, water washing or alkali washing in order to remove the suspending agent. The number of times these washing operations are carried out may be selected optimally from the viewpoints of work efficiency and efficiency of removing the suspending agent, and may be carried out once or may be repeated a number of times. The temperature for washing may be selected optimally in consideration of the efficiency of removing the suspending agent, the degree of coloration of the resulting copolymer, etc., and is preferably 20 to 100°C, more preferably 30 to 95°C, and further preferably 40 to 95°C. The washing time per washing is preferably 10 to 180 minutes, more preferably 20 to 150 minutes, from the viewpoints of washing efficiency, the effect of reducing the angle of repose, and ease of process.

[0090] The pH of the washing solution used during washing may be within a range that allows removal of the suspending agent, and is preferably pH 1-12. The pH when acid washing is carried out is preferably from 1 to 5, more preferably from 1.2 to 4, from the viewpoints of the efficiency of removing the suspending agent and the color tone of the resulting copolymer. The acid used in this case is not particularly limited as long as it is capable of removing the suspending agent, and any conventionally known inorganic acid or organic acid can be used. Suitable acids include inorganic acids such as hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, and boric acid, each of which may be used in the form of a diluted solution diluted with water, etc. Suitable organic acids include those having a carboxyl group, a sulfo group, a hydroxyl group, a thiol group, and an enol group. Considering the effect of removing the suspending agent and the color tone of the resulting resin, nitric acid, sulfuric acid, and organic acids having a carboxyl group are more preferable.

[0091] After the acid washing, it is preferred to further carry out washing with water or washing with an alkali from the viewpoints of the color tone of the resulting polymer and reducing the angle of repose. When alkaline cleaning is performed, the pH of the alkaline solution is preferably 7.1 to 12, more preferably 7.5 to 11, and even more preferably 7.5 to 10.5. The alkaline component used in alkaline cleaning is preferably a tetraalkylammonium hydroxide, an alkali metal hydroxide, an alkaline earth metal hydroxide, or the like. More preferably, it is an alkali metal hydroxide or an alkaline earth metal hydroxide, even more preferably, it is lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, magnesium hydroxide, calcium hydroxide, or barium hydroxide, even more preferably, it is lithium hydroxide, sodium hydroxide, potassium hydroxide, magnesium hydroxide, or calcium hydroxide, and even more preferably, it is sodium hydroxide or potassium hydroxide. These alkaline components can be used by diluting with water or the like to adjust the pH.

[0092] [Dehydration process] As a method for dehydrating the obtained polymer slurry of the methacrylic resin and separating the polymer particles, a conventionally known method can be applied. For example, there may be mentioned a dehydration method using a centrifuge which utilizes centrifugal force to spin off water, and a method in which water is removed by suction on a porous belt or on a filter membrane to separate polymer particles.

[0093] [Drying process] The polymer of the methacrylic resin in a water-containing state obtained through the above-mentioned dehydration step can be dried by a known method and recovered. Examples of the drying method include hot air drying, which involves blowing hot air into a tank from a hot air blower, blow heater, or the like; vacuum drying, which involves drying by reducing the pressure inside the system and then heating it as necessary; barrel drying, which involves rotating the obtained polymer in a container to remove moisture; and spin drying, which involves drying using centrifugal force. These methods may be used alone or in combination. Taking into consideration the handleability, color tone, and the like of the resulting methacrylic resin, the water content of the resulting methacrylic resin is preferably 0.01% by mass to 1% by mass, more preferably 0.05% by mass to 1% by mass, even more preferably 0.1% by mass to 1% by mass, and even more preferably 0.27% by mass to 1% by mass. The water content of the resulting resin can be measured by the Karl Fischer method.

[0094] When the methacrylic resin is produced by the above-mentioned suspension polymerization method, the resulting methacrylic resin is usually substantially spherical, but aggregates may be formed in some cases. The term "agglomerates" refers to residues remaining on a 1.68 mm mesh sieve when the obtained polymer is passed through the sieve. If the aggregates remain in the methacrylic resin, the color tone of the resulting methacrylic resin tends to be deteriorated. From this viewpoint, the amount of aggregates in the methacrylic resin is preferably 1.2% by mass or less, and more preferably 1.0% by mass or less. The content of agglomerates can be determined by passing a sample through a 1.68 mm mesh sieve, drying the material remaining on the sieve in a drying oven at 80°C for 12 hours, measuring its weight, and dividing the resulting mass by the total amount of the raw materials to calculate the amount of agglomerates generated (mass %).

[0095] The average particle size of the methacrylic resin obtained by using the above-mentioned suspension polymerization method is preferably 0.1 mm or more, taking into consideration workability during molding and extrusion, and is more preferably 0.1 mm or more and 1 mm or less, even more preferably 0.1 mm or more and 0.5 mm or less, and even more preferably 0.1 mm or more and 0.4 mm or less, taking into consideration the color tone of the molded piece obtained by molding. The average particle size can be measured, for example, by using sieves (Tokyo Screen JTS-200-45-44 (mesh opening 500 μm), 34 (mesh opening 425 μm), 35 (mesh opening 355 μm), 36 (mesh opening 300 μm), 37 (mesh opening 250 μm), 38 (mesh opening 150 μm), 61 (receiving pan)) based on JIS-Z8801, sieving is performed for 10 minutes at a vibration force of MAX using a sieving tester TSK B-1, measuring the mass of particles remaining on each sieve, and determining the particle size when the mass becomes 50%.

[0096] <Production method using solution polymerization method> Hereinafter, a suitable method for producing a methacrylic resin may include, for example, the solution polymerization method described in Japanese Patent Application Laid-Open No. 2017-125185.

[0097] (Other Ingredients) <Other resins> The methacrylic resin composition of the present embodiment may contain other known resins in combination, so long as the resins can exhibit the properties required for the methacrylic resin composition of the present embodiment. Other resins include thermoplastic resins, and examples of the thermoplastic resins include, but are not limited to, rubber polymers such as acrylic rubber, polyethylene resins, polypropylene resins, polystyrene resins, syndiotactic polystyrene resins, polycarbonate resins, ABS resins, acrylic resins, AS resins, BAAS resins, MBS resins, AAS resins, biodegradable resins, polycarbonate-ABS resin alloys, polyalkylene arylate resins (polybutylene terephthalate, polyethylene terephthalate, polypropylene terephthalate, polytrimethylene terephthalate, polyethylene naphthalate, etc.), polyamide resins, polyphenylene ether resins, polyphenylene sulfide resins, phenolic resins, and the like. In particular, AS resin and BAAS resin are preferred from the viewpoint of improving fluidity, acrylic rubber polymer, ABS resin and MBS resin are preferred from the viewpoint of improving impact resistance, and polyester resin is preferred from the viewpoint of improving chemical resistance. Polycarbonate-based resins are preferred when it is necessary to impart heat resistance, impact resistance, or adjust optical properties, while acrylic-based resins have good compatibility with the above-mentioned methacrylic-based resins and are preferred when it is necessary to adjust properties such as fluidity and impact resistance while maintaining transparency. The above-mentioned various thermoplastic resins may be used alone or in combination of two or more kinds.

[0098] In the methacrylic resin composition used in this embodiment, when the above-mentioned methacrylic resin and the other resin are combined, it is sufficient that the effects of the present invention can be exhibited. However, taking into consideration the effect of imparting characteristics, the blending ratio of the other resin, when a general-purpose acrylic resin is blended as the other resin, is preferably 95% by mass or less, more preferably 85% by mass or less, even more preferably 80% by mass or less, and even more preferably 75% by mass or less, relative to 100% by mass of the total amount of the above-mentioned methacrylic resin and other resins. Furthermore, when a resin other than an acrylic resin is blended as the other resin, the amount is preferably 50% by mass or less, more preferably 45% by mass or less, even more preferably 40% by mass or less, still more preferably 30% by mass or less, and even more preferably 20% by mass or less, relative to 100% by mass of the total amount of the above-mentioned methacrylic resin and other resin. In addition, taking into consideration the effect of imparting characteristics when other resins are blended, the lower limit of the blending amount when other resins are blended is preferably 0.1 mass % or more, more preferably 1 mass % or more, even more preferably 2 mass % or more, still more preferably 3 mass % or more, and even more preferably 5 mass % or more. The type and content of the other resin can be appropriately selected depending on the effect expected when used in combination with the other resin.

[0099] <Additives> In the methacrylic resin composition used in the present embodiment, other additives may be optionally blended. The additives are not particularly limited as long as they can exert the effects of the present invention, and may be appropriately selected depending on the purpose.Examples of additives include, but are not limited to, various stabilizers such as ultraviolet absorbers, heat stabilizers, and light stabilizers; plasticizers (paraffinic process oils, naphthenic process oils, aromatic process oils, paraffins, organic polysiloxanes, and mineral oils); flame retardants (e.g., phosphorus-based, halogen-based, silica-based, and silicone-based additives such as organic phosphorus compounds, red phosphorus, and inorganic phosphates); flame retardant assistants (e.g., antimony oxides, metal oxides, and metal hydroxides); curing agents (diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, diethylaminopropylamine, 3,9-bis(3-aminopropyl)-2,4,8,10-tetraoxaspiro[5,5]undecane, menthenediamine, isophoronediamine, N-aminopropylamine, methyl ... amines such as noethylpiperazine, m-xylenediamine, m-phenylenediamine, diaminophenylmethane, diaminodiphenylsulfone, dicyandiamide, and adipic dihydrazide; phenolic resins such as phenol novolac resin and cresol novolac resin; polymercaptans such as liquid polymercaptan and polysulfide; acid anhydrides such as phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, pyromellitic anhydride, methylcyclohexenetetracarboxylic anhydride, dodecylsuccinic anhydride, trimellitic anhydride, chlorendic anhydride, benzophenonetetracarboxylic anhydride, and ethylene glycol bis(anhydrotrimate);Curing accelerators (imidazoles such as 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-phenyl-4-methylimidazole, etc.; organic phosphines such as triphenylphosphine, tributylphosphine, etc.; tertiary amines such as benzyldimethylamine, 2-dimethylaminomethyl)phenol, 2,4,6-tris(diaminomethyl)phenol, tetramethylhexanediamine, etc.; triphenylphosphine, triphenylphosphine, etc.; boron salts such as fluorophosphine tetraphenylborate, tetraphenylphosphonium tetraphenylborate, triethylamine tetraphenylborate, quinoid compounds such as 1,4-benzoquinone, 1,4-naphthoquinone, 2,3-dimethyl-1,4-benzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-1,4-benzoquinone, etc.); antistatic agents (for example, polyamide elastomers, quaternary ammonium salts, pyridine derivatives, aliphatic sulfonates, aromatic sulfonates, aromatic sulfonate copolymers, sulfate salts, partial esters of polyhydric alcohols, alkyldiethanolamines, alkyldiethanolamides, polyalkylene glycol derivatives, betaines, imidazoline derivatives, etc.; electrical conductivity imparting agents; stress relaxation agents; release agents (alcohols, esters of alcohols and fatty acids, esters of alcohols and dicarboxylic acids, silicone oils, etc.); crystallization accelerators; hydrolysis inhibitors; lubricants (for example, higher fatty acids such as stearic acid, behenic acid, zinc stearate, calcium stearate, magnesium stearate, and the like, and metal salts thereof, higher fatty acid amides such as ethylene bisstearamide, etc.); impact imparting agents; sliding property improvers (hydrocarbons such as low molecular weight polyethylene, higher alcohols, polyhydric alcohols, polyglycols, polyglycerols, higher fatty acids, higher fatty acid metal salts, fatty acid amides, esters of fatty acids and aliphatic alcohols, full or partial esters of fatty acids and polyhydric alcohols, full or partial esters of fatty acids and polyglycols, silicones, fluororesins, etc.); compatibilizers; nucleating agents; reinforcing agents such as fillers; flow control agents;Dyes (nitroso dyes, nitro dyes, azo dyes, stilbene azo dyes, ketoimine dyes, triphenylmethane dyes, xanthene dyes, acridine dyes, quinoline dyes, methine / polymethine dyes, thiazole dyes, indamine / indophenol dyes, azine dyes, oxazine dyes, thiazine dyes, sulfide dyes, aminoketone / oxyketone dyes, anthraquinone dyes, indigoid dyes, phthalocyanine dyes, and other dyes); sensitizers; colorants (inorganic pigments such as titanium oxide, carbon black, titanium yellow, iron oxide pigments, ultramarine blue, cobalt blue, chromium oxide, spinel green, lead chromate pigments, and cadmium pigments; azo pigments such as azo lake pigments, benzimidazolone pigments, diarylide pigments, and condensed azo pigments; phthalocyanine pigments such as phthalocyanine blue and phthalocyanine green; iso Indolinone pigments, quinophthalone pigments, quinacridone pigments, perylene pigments, anthraquinone pigments, perinone pigments, organic pigments such as condensed polycyclic pigments such as dioxazine violet, aluminum flake metallic pigments, spherical aluminum pigments used to improve weld appearance, mica powder for pearl metallic pigments, and other metallic pigments such as polyhedral particles of glass and other inorganic materials coated with metal plating or sputtering; thickeners; anti-settling agents; anti-sagging agents; fillers (fibrous reinforcing agents such as glass fiber and carbon fiber, as well as glass beads, calcium carbonate, talc, clay, etc.); defoamers (silicone-based defoamers, surfactants, polyethers, organic defoamers such as higher alcohols, etc.); coupling agents; light-diffusing fine particles; rust inhibitors; antibacterial and antifungal agents; antifouling agents; conductive polymers, etc.;

[0100] <<Light stabilizers>> A light stabilizer may be added to the methacrylic resin composition used in the present embodiment in order to improve weather resistance. As the light stabilizer, a hindered amine light stabilizer (HALS) can be suitably added. Examples of light stabilizers that can be suitably used include, but are not limited to, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate, 2-(3,5-di-tert-butyl-4-hydroxybenzyl)-2-n-butylmalonate bis(1,2,2,6,6-pentamethyl-4-piperidyl), tetra Examples of such tetracarboxylates include kis(1,2,2,6,6-pentamethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate, 1,2,2,6,6-pentamethyl-4-piperidyl / tridecyl-1,2,3,4-butanetetracarboxylate, and {1,2,2,6,6-pentamethyl-4-piperidyl / β,β,β',β'-tetramethyl-3,9-[2,4,8,10-tetraoxaspiro(5,5)undecane]diethyl}-1,2,3,4butanetetracarboxylate. In addition, dimethyl succinate-1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine polycondensate, N,N'-bis(3-aminopropyl)ethylenediamine-2,4-bis[N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino]-6-chloro-1,3,5-triazine condensate, poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]], poly[{6-(1,1,3- trimethylpentyl)amino-1,3,5-triazine-2,4-diyl}{(N-methyl-2,2,6,6-tetramethyl-piperidyl)imino}octamethylene{(N-methyl-2,2,6,6-tetramethyl-piperidyl)imino}], poly[(6-morpholino-S-triazine-2,4-di)[1,2,2,6,6-pentamethyl-4-piperidyl]imino]-hexamethylene[(1,2,2,6,6-pentamethyl-4-piperidyl)imino]], poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(N-methyl-2,2,6,6-tetramethyl-piperidyl)imino}octamethylene{(N-methyl-2,2,6,6-tetramethyl-piperidyl)imino}] ,4-diyl}{(2,2,6,6-tetramethyl-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-piperidyl)imino}], bis(1,2,2,6,6-pentamethyl-4-piperidyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate, mixture of bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidylsebacate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, N ,N'-Bis(2,2,6,6-tetramethyl-4-piperidyl)-N,N'-diformylhexamethylenediamine, polycondensation product of dibutylamine 1,3,5-triazine, N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}], tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate, 1,2,2,6,6-pentamethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-dicarboxylate Examples of such compounds include a reaction product of ethanol, a reaction product of 2,2,6,6-tetramethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol, bis(1-undecanoxy-2,2,6,6-tetramethylpiperidin-4-yl)carbonate, 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, and 2,2,6,6-tetramethyl-4-piperidyl methacrylate. Among them, from the viewpoint of thermal stability of the light stabilizer, bis(1,2,2,6,6-pentamethyl-4-piperidyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate, which contains three or more ring structures, polycondensation product of dibutylamine 1,3,5-triazine, N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine, and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2 ,4-diyl}{2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}], the reaction product of 1,2,2,6,6-pentamethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol, and 2,2,6,6-tetramethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol are preferably used.

[0101] <<Heat stabilizer>> Examples of the heat stabilizer include, but are not limited to, (a) hindered phenol-based antioxidants, (b-1) phosphorus-based antioxidants, and (b-2) sulfur-based antioxidants. The methacrylic resin composition used in the present embodiment is suitably used in various applications such as melt extrusion, injection molding, film molding, etc. The heat history during processing varies depending on the processing method, ranging from about several tens of seconds in an extruder to several tens of minutes to several hours in the molding processing of thick-walled products and sheet molding. When subjected to a long-term heat history, it is necessary to increase the amount of heat stabilizer added in order to obtain the desired heat stability. From the viewpoint of suppressing bleed-out of the heat stabilizer and preventing the film from sticking to the roll during film formation, it is preferable to use multiple types of heat stabilizers in combination, for example, it is preferable to use at least one selected from (b-1) a phosphorus-based antioxidant and (b-2) a sulfur-based antioxidant in combination with (a) a hindered phenol-based antioxidant. These antioxidants may be used alone or in combination of two or more.

[0102] As the heat stabilizer, from the viewpoint of achieving even better heat stability in air, a binary system using (a) a hindered phenol-based antioxidant and (b-2) a sulfur-based antioxidant, or a binary system using (a) a hindered phenol-based antioxidant and (b-1) a phosphorus-based antioxidant is preferred. From the viewpoint of achieving particularly excellent heat stability in air over the short and long term, a ternary system using three types of antioxidants, namely (a) a hindered phenol-based antioxidant, (b-1) a phosphorus-based antioxidant, and (b-2) a sulfur-based antioxidant, is more preferred.

[0103] Examples of the heat stabilizer include, but are not limited to, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,3',3' ',5,5',5''-Hexa-tert-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, 4,6-bis(dodecylthiomethyl)-o-cresol, ethylene bis(oxyethylene) bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[3-(3,5 -di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris[(4-tert-butyl-3-hydroxy-2,6-xylin)methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6- Examples of the acrylate copolymer include di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamine)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, and 2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate. In particular, pentaerythritol terakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, and 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate are preferred.

[0104] In addition, as the (a) hindered phenol-based antioxidant as the heat stabilizer, a commercially available phenol-based antioxidant may be used. Examples of such commercially available phenol-based antioxidants include, but are not limited to, Irganox 1010 (Irganox 1010: pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], manufactured by BASF), Irganox 1076 (Irganox 1076: octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, manufactured by BASF), Irganox 1330 (Irganox 1330: octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, manufactured by BASF), and the like. 1330: 3,3',3'',5,5',5''-hexa-t-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, manufactured by BASF), Irganox 3114 (Irganox 3114: 1,3,5-tris(3,5-di-t-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, manufactured by BASF), Irganox 3125 (Irganox 3125, manufactured by BASF), Adeka STAB AO-60 (pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], manufactured by ADEKA), Adeka STAB AO-80 (3,9-bis{2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane, manufactured by ADEKA), Sumilizer BHT (Sumilizer BHT, manufactured by Sumitomo Chemical), Cyanox 1790 (Cyanox 1790, manufactured by Cytec), Sumilizer GA-80 (Sumilizer GA-80, manufactured by Sumitomo Chemical), Sumilizer GS (Sumilizer Examples of such compounds include GS (2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, manufactured by Sumitomo Chemical), Sumilizer GM (2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, manufactured by Sumitomo Chemical), and Vitamin E (manufactured by Eisai). Among these commercially available hindered phenol-based antioxidants, Irganox 1010, Adeka STAB AO-60, Adeka STAB AO-80, Irganox 1076, Sumilizer GS, and the like are preferred from the viewpoint of the effect of imparting thermal stability to the resin. These may be used alone or in combination of two or more.

[0105] In addition, examples of the phosphorus-based antioxidant (b-1) as the heat stabilizer include, but are not limited to, tris(2,4-di-t-butylphenyl)phosphite, bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethyl ester phosphorous acid, tetrakis(2,4-di-t-butylphenyl)(1,1-biphenyl)-4,4'-diylbisphosphonate, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-t-butyl-4-methylphenyl)ethyl ester phosphorous acid, and the like. bis(2,4-dicumylphenyl)pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tetrakis(2,4-t-butylphenyl)(1,1-biphenyl)-4,4'-diylbisphosphonite, di-t-butyl-m-cresyl-phosphonite, 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, and the like.

[0106] Furthermore, commercially available phosphorus-based antioxidants may be used as the phosphorus-based antioxidant. Examples of commercially available phosphorus-based antioxidants include, but are not limited to, Irgafos 168 (Irgafos 168: tris(2,4-di-t-butylphenyl)phosphite, manufactured by BASF), Irgafos 12 (Irgafos 12: tris[2-[[2,4,8,10-tetra-t-butyldibenzo[d,f][1,3,2]dioxaphosphen-6-yl]oxy]ethyl]amine, manufactured by BASF), Irgafos 38 (Irgafos 38: bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethyl ester phosphorous acid, manufactured by BASF), ADK STAB 329K (ADK STAB-329K, manufactured by ADEKA), ADK STAB PEP-36 (ADK STAB PEP-36, manufactured by ADEKA), ADK STAB PEP-36A, ADK STAB PEP-8, ADK STAB HP-10, ADK STAB HP-10, ADK STAB 2112, manufactured by ADEKA, ADK STAB 1178, manufactured by ADEKA, ADK STAB 1500, manufactured by ADEKA, Sandstab P-EPQ, manufactured by Clariant, Weston 618, manufactured by GE, Weston 619G, manufactured by GE, Ultranox 626, manufactured by GE, Sumilizer GP GP: 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, manufactured by Sumitomo Chemical Co., Ltd.), HCA (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, manufactured by Sanko Co., Ltd.), and the like. Among these commercially available phosphorus-based antioxidants, from the viewpoint of the effect of imparting thermal stability to the resin and the effect of using them in combination with various other antioxidants, Irgafos 168, ADK STAB PEP-36, ADK STAB PEP-36A, ADK STAB HP-10, and ADK STAB 1178 are preferred, with ADK STAB PEP-36A and ADK STAB PEP-36 being particularly preferred. These phosphorus-based antioxidants may be used alone or in combination of two or more kinds.

[0107] In addition, examples of the sulfur-based antioxidant (b-2) as the heat stabilizer include, but are not limited to, 2,4-bis(dodecylthiomethyl)-6-methylphenol (Irganox 1726, manufactured by BASF), Irganox 1520L, manufactured by BASF), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthio]propionate] (Adekastab AO-412S, manufactured by ADEKA), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthio]propionate] (ChemiNox PLS, manufactured by Chemipro Chemical Co., Ltd.), and di(tridecyl) 3,3'-thiodipropionate (AO-503, manufactured by ADEKA). Among these commercially available sulfur antioxidants, ADK STAB AO-412S and Cheminox PLS are preferred from the viewpoints of the effect of imparting thermal stability to the resin, the effect of using them in combination with various antioxidants, and ease of handling. These sulfur-based antioxidants may be used alone or in combination of two or more kinds.

[0108] The content of the heat stabilizer may be any amount that provides the effect of improving heat stability. If the content is excessive, problems such as bleeding out during processing may occur, so the content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 1 part by mass or less, even more preferably 0.8 parts by mass or less, still more preferably 0.01 to 0.8 parts by mass, and particularly preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the methacrylic resin. In addition, from the viewpoint of suppressing the thermal decomposition of the methacrylic resin, suppressing the deterioration of the color tone of the obtained molded body, and suppressing the volatilization of the heat stabilizer to suppress the occurrence of silver streaks during molding processing, it is preferable that the methacrylic resin contains 0.01 to 2 parts by mass (preferably 0.02 to 1 part by mass) of (a) hindered phenol-based antioxidant and contains 0.01 to 2 parts by mass (preferably 0.01 to 1 part by mass) of (b-1) phosphorus-based antioxidant and (b-2) sulfur-based antioxidant in total, relative to 100 parts by mass of the methacrylic resin. From the same viewpoint, it is preferable that the methacrylic resin contains 0.01 to 2 parts by mass (preferably 0.02 to 1 part by mass) of (a) hindered phenol-based antioxidant and contains 0.01 to 2 parts by mass (preferably 0.01 to 1 part by mass) of (b-1) phosphorus-based antioxidant and / or (b-2) sulfur-based antioxidant in total, relative to 100 parts by mass of the methacrylic resin.

[0109] <<Lubricants>> Examples of the lubricant include, but are not limited to, fatty acid esters, fatty acid amides, fatty acid metal salts, hydrocarbon-based lubricants, and alcohol-based lubricants.

[0110] The fatty acid ester that can be used as the lubricant is not particularly limited, and any of the conventionally known fatty acid esters can be used. Examples of fatty acid esters that can be used include ester compounds of fatty acids having 12 to 32 carbon atoms, such as lauric acid, palmitic acid, heptadecanoic acid, stearic acid, oleic acid, arachic acid, and behenic acid, with monohydric aliphatic alcohols, such as palmityl alcohol, stearyl alcohol, and behenyl alcohol, and polyhydric aliphatic alcohols, such as glycerin, pentaerythritol, dipentaerythritol, and sorbitan; and complex ester compounds of fatty acids, polybasic organic acids, and monohydric aliphatic alcohols or polyhydric aliphatic alcohols. Examples of such fatty acid ester lubricants include cetyl palmitate, butyl stearate, stearyl stearate, stearyl citrate, glycerin monocaprylate, glycerin monocaprate, glycerin monolaurate, glycerin monopalmitate, glycerin dipalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, glycerin monooleate, glycerin dioleate, glycerin trioleate, glycerin monolinoleate, and the like. glycerin monobehenate, glycerin mono 12-hydroxystearate, glycerin di 12-hydroxystearate, glycerin tri 12-hydroxystearate, glycerin diacetomonostearate, glycerin citrate fatty acid ester, pentaerythritol adipic acid stearate, partially saponified montanic acid ester, pentaerythritol tetrastearate, dipentaerythritol hexastearate, and sorbitan tristearate. These fatty acid ester-based lubricants can be used alone or in combination of two or more. Examples of commercially available products include, but are not limited to, the Rikemal series, Poem series, Rikestar series, and Rikemaster series manufactured by Riken Vitamin Co., Ltd., and the Excel series, Leodor series, Exepar series, and Coconard series manufactured by Kao Corporation, and more specific examples include Rikemal S-100, Rikemal H-100, Poem V-100, Rikemal B-100, Rikemal HC-100, Rikemal S-200, Poem B-200, Rikestar EW-200, Rikestar EW-400, Excel S-95, and Leodor MS-50.

[0111] The fatty acid amide-based lubricant is not particularly limited, and any of the conventionally known lubricants can be used. Examples of fatty acid amide lubricants include saturated fatty acid amides such as lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, and hydroxystearic acid amide; unsaturated fatty acid amides such as oleic acid amide, erucic acid amide, and ricinoleic acid amide; substituted amides such as N-stearyl stearic acid amide, N-oleyl oleic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, N-stearyl erucic acid amide, and N-oleyl palmitic acid amide; methylol amides such as methylol stearic acid amide and methylol behenic acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, and ethylene bisstearic acid amide (ethylene saturated fatty acid bisamides such as ethylene bisstearylamide, ethylene bisisostearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene bishydroxystearic acid amide, N,N'-distearyl adipamide, and N,N'-distearyl sebacic acid amide; unsaturated fatty acid bisamides such as ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipamide, and N,N'-dioleyl sebacic acid amide; and aromatic bisamides such as m-xylylene bisstearic acid amide and N,N'-distearyl isophthalic acid amide. These fatty acid amide-based lubricants can be used alone or in combination of two or more. Examples of commercially available products include, but are not limited to, the Diamid series (manufactured by Nippon Kasei Chemical Industry Co., Ltd.), the Amide series (manufactured by Nippon Kasei Chemical Industry Co., Ltd.), the Nikka Amide series (manufactured by Nippon Kasei Chemical Industry Co., Ltd.), the Methylol Amide series, the Bis Amide series, the Slipax series (manufactured by Nippon Kasei Chemical Industry Co., Ltd.), the Kaowax series (manufactured by Kao Corporation), the Fatty Acid Amide series (manufactured by Kao Corporation), and ethylene bis stearic acid amides (manufactured by Dainichi Chemical Industry Co., Ltd.).

[0112] The fatty acid metal salt refers to a metal salt of a higher fatty acid, and includes, but is not limited to, for example, lithium stearate, magnesium stearate, calcium stearate, calcium laurate, calcium ricinoleate, strontium stearate, barium stearate, barium laurate, barium ricinoleate, zinc stearate, zinc laurate, zinc ricinoleate, zinc 2-ethylhexoate, lead stearate, dibasic lead stearate, lead naphthenate, calcium 12-hydroxystearate, lithium 12-hydroxystearate, and the like. Among these, calcium stearate, magnesium stearate, and zinc stearate are particularly preferred because the resulting methacrylic resin composition has excellent processability and extremely excellent transparency. Examples of commercially available products include the SZ series, SC series, SM series, and SA series manufactured by Sakai Chemical Industry Co., Ltd. When the fatty acid metal salt is used, the blending amount is preferably 0.2% by mass or less from the viewpoint of maintaining transparency.

[0113] The lubricants may be used alone or in combination of two or more. The lubricant to be used preferably has a decomposition onset temperature of 200° C. or higher. The decomposition onset temperature can be measured by the 1% weight loss temperature using TGA.

[0114] The content of the lubricant may be an amount sufficient to obtain the effect as a lubricant. If the content is excessive, problems such as bleed-out during processing or poor extrusion due to screw slippage may occur. Therefore, the content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 1 part by mass or less, still more preferably 0.8 parts by mass or less, still more preferably 0.01 to 0.8 parts by mass, and particularly preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the methacrylic resin. Addition of an amount within the above range is preferable because it suppresses the decrease in transparency caused by the addition of a lubricant, tends to suppress sticking to metal rolls during film formation, and makes it less likely that problems such as peeling will occur in long-term reliability tests after secondary processing of the film, such as the application of a primer.

[0115] <<Ultraviolet absorbing agent>> Examples of the ultraviolet absorber include, but are not limited to, benzotriazole-based compounds, benzotriazine-based compounds, benzoate-based compounds, benzophenone-based compounds, oxybenzophenone-based compounds, phenol-based compounds, oxazole-based compounds, malonic acid ester-based compounds, cyanoacrylate-based compounds, lactone-based compounds, salicylic acid ester-based compounds, and benzoxazinone-based compounds.

[0116] Examples of benzotriazole compounds include, but are not limited to, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(2H-benzotriazol-2-yl)-p-cresol, 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-benzotriazol-2-yl-4,6-di-tert-butylphenol, 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-t-butylphenol, 2-(2H-benzotriazol-2-yl)-4,6-di-t-butylphenol, 2-(2H-benzotriazol-2-yl)-4,6-di-t-butylphenol, 2-(2H-benzotriazol-2-yl)-4-methyl-6-(3,4,5,6-tetrahydrophthalimidylmethyl)phenol, methyl 3-(3-(2H-benzotriazol-2-yl)-5-t-butyl-4-hydroxyphenyl)propionate / polyethylene glycol 300 reaction products, 2-(2H-benzotriazol-2-yl)-6-(linear and side chain dodecyl)-4-methylphenol, 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy-C7-9 side chain and linear alkyl esters.

[0117] Examples of benzotriazine compounds include, but are not limited to, 2-mono(hydroxyphenyl)-1,3,5-triazine compounds, 2,4-bis(hydroxyphenyl)-1,3,5-triazine compounds, and 2,4,6-tris(hydroxyphenyl)-1,3,5-triazine compounds. Specific examples of benzotriazine compounds include 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, and 2,4-diphenyl-(2 -Hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine )-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyethoxy)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-dibutoxyphenyl)-1,3-5-triazine, 2,4,6-tris(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2, 4,6-tris(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-methoxycarbonylpropyloxyphenyl)-1,3,5-triazine 2,4,6-tris(2-hydroxy-4-ethoxycarbonylethyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-(1-(2-ethoxyhexyloxy)-1-oxopropan-2-yloxy)phenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-methoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3 -methyl-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy -3-methyl-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,Examples of the tris(2-hydroxy-3-methyl-4-methoxycarbonylpropyloxyphenyl)-1,3,5-triazine include 6-tris(2-hydroxy-3-methyl-4-methoxycarbonylethyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxycarbonylethyloxyphenyl)-1,3,5-triazine, and 2,4,6-tris(2-hydroxy-3-methyl-4-(1-(2-ethoxyhexyloxy)-1-oxopropan-2-yloxy)phenyl)-1,3,5-triazine.

[0118] Among these, ultraviolet absorbers having a 2,4-bis(2,4-dimethylphenyl)-6-[2-hydroxy-4-(3-alkyloxy-2-hydroxypropyloxy)-5-α-cumylphenyl]-s-triazine skeleton (where "alkyloxy" refers to a long-chain alkyloxy group such as octyloxy, nonyloxy, decyloxy, etc.) are preferred because they have high compatibility with amorphous thermoplastic resins, particularly acrylic resins, and have excellent absorption properties.

[0119] As the ultraviolet absorber, benzotriazole-based compounds and benzotriazine-based compounds are particularly preferred from the viewpoints of compatibility with the resin and volatility upon heating. These ultraviolet absorbents may be used alone or in combination of two or more.

[0120] The melting point (Tm) of the ultraviolet absorber is preferably 80° C. or higher, more preferably 100° C. or higher, even more preferably 130° C. or higher, and even more preferably 160° C. or higher. The ultraviolet absorber preferably exhibits a mass loss rate of 50% or less, more preferably 30% or less, even more preferably 15% or less, even more preferably 10% or less, and even more preferably 5% or less when heated from 23°C to 260°C at a rate of 20°C / min.

[0121] The blending amount of the ultraviolet absorber may be an amount that does not inhibit heat resistance, moist heat resistance, thermal stability, and moldability, and that exerts the effects of the present invention; however, if a large amount is added, problems such as bleeding out during processing may occur, and therefore the blending amount is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 2.5 parts by mass or less, even more preferably 2 parts by mass or less, and even more preferably 1.8 parts by mass or less, relative to 100 parts by mass of the methacrylic resin, and from the viewpoint of exerting the effects of the blending, it is preferably 0.01 parts by mass or more.

[0122] (Characteristics of methacrylic resin composition) The characteristics of the methacrylic resin composition are described below.

[0123] <Weight average molecular weight, molecular weight distribution> The weight average molecular weight (Mw) of the methacrylic resin composition used in this embodiment is 65,000 to 300,000 from the viewpoint of obtaining a methacrylic resin composition having even more excellent mechanical strength, solvent resistance, and flowability. By setting the weight average molecular weight of the methacrylic resin composition within the above range, the methacrylic resin composition becomes excellent in mechanical strength such as Charpy impact strength and in fluidity. From the viewpoint of maintaining mechanical strength, the weight average molecular weight is preferably 65,000 or more, more preferably 70,000 or more, even more preferably 80,000 or more, and still more preferably 100,000 or more. In addition, from the viewpoints of ensuring flowability during molding, reducing distortion during molding, and imparting long path transmittance, the weight average molecular weight is preferably 250,000 or less, more preferably 200,000 or less, even more preferably 150,000 or less, even more preferably 130,000 or less, and still more preferably 120,000 or less. From the viewpoint of a balance between fluidity, mechanical strength, and solvent resistance, the molecular weight distribution (weight average molecular weight (Mw) / number average molecular weight (Mn)) of the methacrylic resin composition is preferably 1.5 to 5. It is more preferably 1.5 to 4.5, even more preferably 1.6 to 4, even more preferably 1.6 to 3, and still more preferably 1.6 to 2.5. The weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin composition can be measured by gel permeation chromatography (GPC). In detail, a calibration curve is prepared from the elution time and the weight average molecular weight using a standard methacrylic resin that is available as a reagent and has a known monodisperse weight average molecular weight, number average molecular weight, and peak molecular weight, and an analytical gel column that elutes high molecular weight components first. Next, the weight average molecular weight and number average molecular weight of the sample of the methacrylic resin composition to be measured can be obtained from the obtained calibration curve. Specifically, it can be measured by the method described in the Examples below.

[0124] <Heat resistance> As an index of heat resistance, the VICAT softening temperature can be used. From the viewpoint of heat resistance during actual use, the Vicat softening temperature of the methacrylic resin composition used in this embodiment is preferably 113° C. or higher, and more preferably 115° C. or higher. The higher the heat resistance, the more stable the dimensions of the molded product will be when it is used as an oil level gauge even when exposed to the heat of the internal oil, motor, etc., and the oil level gauge can be used with excellent reading accuracy. The Vicat softening temperature can be measured in accordance with ISO306 B50, specifically, by the method described in the examples below.

[0125] <Transparency> As an index of transparency, total light transmittance can be used. The total light transmittance of the methacrylic resin composition used in this embodiment may be appropriately optimized depending on the application, but when used for an application requiring transparency, from the viewpoint of visibility, the total light transmittance at a thickness of 3 mm is preferably 80% or more, more preferably 85% or more, even more preferably 88% or more, and even more preferably 90% or more. A higher total light transmittance is preferable because it ensures good visibility of the scale when it is used as an oil level gauge, which is molded to be relatively thick among other molded products. However, in practice, sufficient visibility can be ensured even with a total light transmittance of 94% or less. The total light transmittance can be measured by the method described in the examples described below.

[0126] <Change in YI value during retention> When a resin composition is subjected to a heat history such as molding, it may be exposed to high temperatures for a long time due to troubleshooting, etc. In particular, since an oil level gauge is a thick-walled molded product, it is exposed to high temperatures for a long time during processing, and may turn yellow due to the heat history during processing. According to the methacrylic resin composition of the present embodiment, the degree of change (ΔYI) between the YI when subjected to a short-term thermal history and the YI when subjected to a long-term thermal history can be suppressed. For example, when the methacrylic resin composition of this embodiment is used to prepare test pieces having a thickness of 3 mm, a width of 20 mm, and a length of 220 mm using an injection molding machine (EC-100SX, manufactured by Toshiba Machine Co., Ltd.) under conditions of a molding temperature of 280°C and a mold temperature of 60°C, and the injection molding cycle time (injection time + cooling time) is set to a normal cycle of (c) 45 seconds and an assumed residence time in the molding machine of (d) 270 seconds, the YI value can be estimated by measuring the 220 mm long optical path YI value of five test pieces each of the test pieces obtained at cycle time (c) and the test pieces obtained at cycle time (d) using the test pieces from the 11th shot to the 15th shot after molding has stabilized. The average value of the YI values ​​of the five test pieces in (c) and the average value of the YI values ​​of the five test pieces in (d) were calculated, and the degree of change in the YI values ​​was calculated using the following formula, which can be used as an index of evaluation. Degree of change in YI value = [average YI value of (d) - average YI value of (c)] / average YI value of (c) The degree of change (ΔYI) of the above YI (220 mm) must be 20 or less, and is preferably 18 or less, more preferably 15 or less, even more preferably 13 or less, and still more preferably 10 or less. By having the degree of change (ΔYI) of YI (220 mm) be 20 or less, it is possible to manufacture an oil level gauge having good color tone and visibility even in a molding process that is exposed to high temperatures and has a long processing time. The means for achieving the above-mentioned degree of change (ΔYI) include making the content of styrene monomer units equal to or less than a predetermined amount, incorporating a small amount of a compound (D) represented by general formula (1) or (2) described later, making the ratio of the content of the (D) component to the content of the structural unit (B) having a ring structure in the main chain within a specific range, making Mw equal to or greater than a predetermined level, and the like, and these may be used alone or in combination. The YI value can be measured in accordance with JIS K7105 using a color difference meter (Tokyo Denshoku Co., Ltd., TC-8600A, light source: 10-C), and specifically, can be measured by the method described in the examples described later.

[0127] <Thickness dependence of total light transmittance and ΔYI> In the methacrylic resin composition of this embodiment, the attenuation rate of the total light transmittance at a thickness of 3 mm to 220 mm, represented by the following formula, is preferably 40% or less, more preferably 33% or less, even more preferably 15% or less, and even more preferably 11% or less. Attenuation rate of total light transmittance (%)=100×(Y(3mm)-Y(220mm)) / Y(3mm) When the attenuation rate of the total light transmittance is within the above preferred range, when the oil gauge is used as an oil gauge and has a scale on its surface, the difference in visibility between the oil inside the oil gauge becomes small, making it easier to read the scale. In addition, in the methacrylic resin composition of this embodiment, ΔYI from a thickness of 3 mm to a thickness of 220 mm, represented by the following formula, is preferably 40 or less, more preferably 15 or less, even more preferably 5 or less, and even more preferably 2 or less. ΔYI = YI (220 mm) - YI (3 mm) When ΔYI is in the above preferred range, when the oil gauge is used, the difference in color tone between the oil-filled portion and the portion not filled with oil becomes small, and visibility is excellent.

[0128] <Appearance> The appearance of the methacrylic resin composition of the present embodiment can be evaluated based on, for example, the presence or absence of bubbles, streaks, silver streaks, and the like. In the methacrylic resin composition of the present embodiment, the methacrylic resin composition is dried at 80° C. for 24 hours, and then 50 test pieces are molded using an injection molding machine and a measuring mold. Of these, the number of test pieces on which silver streaks are observed on the surface is preferably 10 or less, more preferably 5 or less, and even more preferably 2 or less. Good appearance leads to good productivity of the oil gauge. The presence or absence of silver streaks in the methacrylic resin composition can be evaluated by the method described in the Examples below.

[0129] <Weather resistance> The weather resistance of the methacrylic resin composition of the present embodiment can be evaluated by measuring the color difference (ΔE*) of a sample before and after an exposure test. For example, the methacrylic resin composition of this embodiment is molded using an injection molding machine (EC-100SX, manufactured by Toshiba Machine Co., Ltd.) under conditions of resin temperature: 280°C, mold temperature: 70°C to prepare a long optical path test piece having a thickness of 3 mm, width of 20 mm, and length of 220 mm. Using this 3 mm thick test piece, an exposure test is performed using the method of JIS K7350-4 for a total exposure time of 2040 hours, and the color difference (ΔE*) before and after the exposure test can be measured using a color difference meter in accordance with JIS Z8730. In the methacrylic resin composition of the present embodiment, the color difference (ΔE*) in the above evaluation is preferably less than 3, more preferably less than 2.5, and even more preferably 2 or less. When ΔE* is within the above-mentioned preferable range, the oil gauge can maintain a stable color tone even when used for a long period of time, making it easy to recognize the deterioration of the internal oil. The means for achieving the above-mentioned gradient color difference (ΔE*) include making the content of styrene monomer units equal to or less than a predetermined amount, incorporating a small amount of a compound (D) represented by the general formula (1) or (2) described later, making the ratio of the content of the (D) component to the content of the structural unit (B) having a ring structure in the main chain within a specific range, making Mw equal to or greater than a predetermined level, and the like, and these may be used alone or in combination. The color difference (ΔE*) can be specifically measured by the method described in the examples below.

[0130] In particular, from the viewpoints of heat resistance, suppression of silver smearing during molding, and hue, the amount of remaining component (A), i.e., methacrylic acid ester monomer, in the methacrylic resin composition is preferably 1 mass% or less, more preferably 0.7 mass% or less, even more preferably 0.5 mass% or less, still more preferably 0.3 mass% or less, and even more preferably 0.2 mass% or less. In particular, the content of the monomer component derived from the (B) component remaining in the methacrylic resin composition is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, even more preferably 0.2% by mass or less, even more preferably 0.15% by mass or less, and even more preferably 0.1% by mass or less, when the methacrylic resin composition is taken as 100% by mass, from the viewpoint of improving the yellowness and transmittance of the molded piece. It is also preferable to keep the amount of remaining monomer low, but if the amount of remaining monomer is reduced as much as possible, the process may become complicated, and productivity may be affected. In consideration of the hue and productivity, the content of the remaining (B) component is preferably 0.001% by mass or more, more preferably 0.005% by mass or more, even more preferably 0.011% by mass or more, and even more preferably 0.02% by mass or more. The content of the residual monomer can be evaluated by the method described in the Examples below.

[0131] (Methacrylic resin composition manufacturing method) The methacrylic resin composition of the present embodiment can be produced by melt-kneading the above-mentioned methacrylic resin, the compound (D) represented by the general formula (1) or (2), and, as necessary, other resins, additives, and the like. Examples of the method for producing the methacrylic resin composition include a method of kneading using a kneading machine such as an extruder, a heating roll, a kneader, a roller mixer, a Banbury mixer, etc. Among these, kneading using an extruder is preferred from the viewpoint of productivity. The kneading temperature may be determined according to the preferred processing temperatures of the polymer constituting the methacrylic resin and the other resins to be mixed, and is generally in the range of 140 to 300°C, preferably 180 to 280°C. It is also preferable to provide the extruder with a vent port in order to reduce volatile content.

[0132] (Molded body) The molded article used as the oil level gauge of this embodiment may contain 80% by mass or more, preferably 90% by mass or more, and more preferably 95% by mass or more of the above-mentioned methacrylic resin composition of this embodiment, and may be made of (including 100% by mass) the above-mentioned methacrylic resin composition of this embodiment.

[0133] The shape of the molded article of this embodiment may be determined appropriately depending on the purpose and application of the oil level gauge.

[0134] The thickness of the oil level gauge of this embodiment is preferably 0.01 to 30 mm from the viewpoint of excellent handling and strength, and also from the viewpoint of excellent optical properties when the molded article of this embodiment is used as an optical component. From the viewpoint of strength, the thickness is more preferably 3 to 25 mm, and further preferably 5 to 20 mm. The thickness of the oil level gauge refers to the thickness of the thinnest part of the molded article excluding the liquid filling part and the mounting part, and can be measured with a vernier caliper, a thickness gauge, or the like.

[0135] (Method of Manufacturing Molded Product) The molded article of the present embodiment can be produced by molding the methacrylic resin composition of the present embodiment. As a method for producing a molded body, known methods such as injection molding, sheet molding, blow molding, injection blow molding, inflation molding, T-die molding, press molding, extrusion molding, foam molding, cast molding, etc. can be applied, and secondary processing molding methods such as compressed air molding and vacuum molding can also be used. Another example of a method for producing a molded article includes a method in which a methacrylic resin composition is kneaded and produced using a kneading machine such as a heated roll, a kneader, a Banbury mixer, or an extruder, and then cooled and pulverized, and then molded by transfer molding, injection molding, compression molding, or the like.

[0136] The oil level gauge of this embodiment may be a component having a rectangular parallelepiped appearance for measuring the amount of engine oil in industrial equipment such as automobiles, and the configuration of such a component is not particularly limited, but may include, for example, vertical holes present at two horizontal ends and penetrating vertically, and a horizontal hole located between the two vertical holes, extending horizontally and penetrating the two vertical holes. EXAMPLES

[0137] Hereinafter, the present embodiment will be described with reference to specific examples and comparative examples, but the present embodiment is not limited to the examples described below.

[0138] [Raw materials] The following examples 、Reference example The raw materials used in the comparative examples are shown below.

[0139] (Monomers that make up methacrylic resins) <(A) Methacrylic acid ester monomer> <<(A-1)>> Methyl methacrylate (MMA): manufactured by Asahi Kasei Corporation (containing 2.5 ppm of 2,4-dimethyl-6-tert-butylphenol manufactured by Chugai Boeki Co., Ltd. as a polymerization inhibitor)

[0140] <(B) Monomer for forming a structural unit having a ring structure in the main chain> <<(B-1-1) Maleimide structural unit>> N-Phenylmaleimide (N-PMI): Nippon Shokubai Co., Ltd. <<(B-1-2) Maleimide structural unit>> N-Cyclohexylmaleimide (N-CMI): Synthesized using the following manufacturing method. A flask equipped with a thermometer, a Dean-Stark tube, a dropping funnel, and a stirrer was charged with maleic anhydride and six times the amount of ortho-xylene per unit mass of maleic anhydride, and the mixture was heated to 55°C and stirred to prepare a uniform ortho-xylene solution of maleic anhydride. Next, a solution containing an equivalent amount of cyclohexylamine in terms of molar ratio to maleic anhydride and an equal mass of ortho-xylene was added dropwise to the maleic anhydride solution at 55°C over a period of 30 minutes with stirring to synthesize a slurry of N-cyclohexylmaleamic acid in ortho-xylene. Next, the slurry was added with the same mass of orthophosphoric acid as cyclohexylamine as an acid catalyst, and 200 ppm of copper dibutyldithiocarbamate relative to N-cyclohexylmaleamic acid as a polymerization inhibitor, and the mixture was heated and stirred at 140°C, and the reaction was carried out for 8 hours while the water generated by the reaction was distilled out of the reaction system using a Dean-Stark tube. After the reaction was completed, the acid catalyst layer separated into the lower layer from the reaction solution at 140°C was separated and removed. The reaction solution was then washed twice with 3% by mass sulfuric acid water and twice with ion-exchanged water, and ortho-xylene was removed from the organic layer under a reduced pressure of 10 mmHg. The mixture was then distilled and purified under a reduced pressure of 5 mmHg at an internal temperature of 130 to 150°C to obtain a raw material mainly composed of white N-cyclohexylmaleimide. <<(B-3) Glutarimide structural unit>> Methyl methacrylate (MMA): <<(A-1)>> as described above. Methacrylic acid (MA): manufactured by Tokyo Chemical Industry Co., Ltd.

[0141] <(C) Vinyl monomer> <<(C-1)>> Styrene (St): Asahi Kasei Corporation <<(C-2)>> Methacrylic acid (MA): manufactured by Tokyo Chemical Industry Co., Ltd. <<(C-3>> Methyl acrylate: manufactured by Tokyo Chemical Industry Co., Ltd.

[0142] <(D) Compound> <<(D-1)>> N-Cyclohexyl-2-hydroxysuccinimide: The initial distillate obtained during the production of (B-2) was used to repeatedly perform recrystallization purification to obtain needle-like crystals of the component (D-1).

[0143] (Organic solvent) Meta-xylene: Mitsui Chemicals, Inc.

[0144] (others) · n-Octylmercaptan (NOM): manufactured by Arkema Co., Ltd., used as a chain transfer agent. Perhexa C-75 (EB): NOF Corporation, purity 75% (contains 25% ethylbenzene), used as a polymerization initiator. t-Butyl peroxy-2-ethylhexanoate: manufactured by NOF Corporation. Used as a polymerization initiator. - Calcium phosphate: Manufactured by Nippon Chemical Industry Co., Ltd., used as a suspending agent and used it. ·Calcium carbonate: manufactured by Shiraishi Kogyo Co., Ltd., used as a suspending agent. Sodium lauryl sulfate: manufactured by Wako Pure Chemical Industries, Ltd., used as a suspension aid.

[0145] <Additives> < <a-1>> AD2112: ADEKA Corporation < <a-2>> - ADK STAB AO-80: ADEKA Corporation < <a-3>> Tinuvin P: BASF

[0146] Methods for measuring the properties of the methacrylic resin and the methacrylic resin composition will be described below.

[0147] (I. Measurement of weight average molecular weight of methacrylic resin and methacrylic resin composition) Methacrylic resins produced in the following production examples and examples 、Reference example The weight average molecular weight (Mw) of the methacrylic resin in the methacrylic resin composition produced in the above step was measured using the following device and conditions. Measurement equipment: Tosoh Corporation, gel permeation chromatography (HLC-8320GPC) Measurement conditions: Columns: One TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 were used in series. In this column, high molecular weight molecules elute early and low molecular weight molecules elute late. Developing solvent: tetrahydrofuran, flow rate: 0.6 mL / min, 2,6-di-t-butyl-4-methylphenol (BHT) was added at 0.1 g / L as an internal standard. Detector: RI (differential refractometer) detector Detection sensitivity: 3.0mV / min Column temperature: 40℃ Sample: 0.02 g of methacrylic resin in 20 mL of tetrahydrofuran Injection volume: 10μL Standard sample for calibration curve: The following ten types of polymethyl methacrylate (PMMA Calibration Kit MM-10, manufactured by Polymer Laboratories) with known monodisperse weight peak molecular weights and different molecular weights were used. Weight peak molecular weight (Mp) Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard sample 10 850 Under the above conditions, the RI detection intensity with respect to the elution time of the methacrylic resin was measured. Based on the area of the GPC elution curve and the calibration curve of the cubic approximation formula, the weight average molecular weight (Mw) of the methacrylic resin and the methacrylic resin composition was determined. The results are shown in Table 1.

[0148] (II. Measurement of the composition of monomer units of the polymer and the amount of residual monomer) <II-1. Measurement of the composition of monomer units> For the obtained methacrylic resin and the obtained methacrylic resin composition, NMR and FT-IR measurements were carried out to confirm the composition of monomer units and structural units. NMR: JNM-ECA500 manufactured by JEOL Ltd. FT-IR: IR-410 manufactured by JASCO Corporation, ATR method (Dura Scope (ATR crystal: diamond / ZnSe), resolution: 4 cm -1 ) was used. <II-2. Measurement of the amount of residual monomer> Measurement was carried out by the calibration curve method using GC. More specifically, a part of the obtained methacrylic resin composition was sampled and weighed, This sample was dissolved in chloroform to prepare a 0.5 mass% solution, and nonane was added as an internal standard substance. A capillary column (manufactured by Phenomenex, product number: ZB-1) with an inner diameter of 0.32 mm and a length of 30 m was used for the FID-type gas chromatography (product number: GC2025) manufactured by Shimadzu Corporation. In the measurement, after holding at 45 °C for 5 minutes, the temperature was raised to 110 °C at a rate of 10 °C / min, then to 200 °C at 30 °C / min, further to 240 °C at 10 °C / min, then to 300 °C at 50 °C / min, and held at 300 °C for 10 minutes.

[0149] (III. Physical Property Measurement) The evaluation methods of methacrylic resins and methacrylic resin compositions are described below.

[0150] <III-1. Heat Resistance; Measurement of Vicat Softening Temperature> The resin pellets obtained in the examples 、Reference example and comparative examples described later were used to mold 4 mm thick test pieces, and in accordance with ISO 306 B50, the Vicat softening temperature (°C) was measured and used as an index for heat resistance evaluation.

[0151] <III-2. Transparency (Optical Property); Measurement of Total Light Transmittance> The resin pellets obtained in the examples 、Reference example and comparative examples described later were used to injection mold 3 mm thick test pieces, and in accordance with JIS K7361-1 standard, the total light transmittance was measured. It is preferably 90% or more of the total light transmittance, which is at the same level as a general commercially available acrylic resin (PMMA).

[0152] <III-3. Degree of Change in YI Value (ΔYI)> The methacrylic resins and resin compositions obtained in the examples 、Reference example and comparative examples described later were used to produce test pieces with a thickness of 3 mm × width of 20 mm × length of 220 mm using an injection molding machine (EC-100SX, manufactured by Toshiba Machine Co., Ltd.) under the conditions of a molding temperature of 280 °C and a mold temperature of 60 °C. The cycle time (injection time + cooling time) of injection molding was set to (c) 45 seconds or (d) 270 seconds. Using the test pieces from the 11th shot to the 15th shot after the molding became stable, the YI values of the test pieces obtained with cycle times (c) and (d), five each, were measured for a 220 mm long optical path. Then, the average value of the YI values of the five test pieces of (c) and the average value of the YI values of the five test pieces of (d) were obtained, and the degree of change in the YI value (ΔYI) for a 220 mm long optical path was calculated from [(average value of YI value of (d) - average value of YI value of (c)) / average value of YI value of (c)]. The YI value was measured in accordance with JIS K7105 using a color difference meter (manufactured by Tokyo Denshoku Co., Ltd., TC-8600A, light source: 10-C). <Long-term retention evaluation> The change degree of the above YI value was evaluated as "◎" when it was 10 or less, "○" when it exceeded 10 and was 13 or less, "△" when it was 20 or less, and "×" when it exceeded 20.

[0153] <Thickness dependence of total light transmittance and ΔYI> Using the same measurement method as in the above (III-2), the total light transmittance Y(3mm) at a thickness of 3 mm and the total light transmittance Y(220mm) at a thickness of 220 mm were measured, and 100×(Y(3mm) - Y(220mm)) / Y(3mm) was taken as the attenuation rate (%) of the total light transmittance. Also, using the same measurement method as in the above (III-3), YI(3mm) at a thickness of 3 mm and YI(220mm) at a thickness of 220 mm were measured, and ΔYI was obtained from the difference (YI(220mm) - YI(3mm)).

[0154] <III-4. Presence or absence of silver streaks> Examples described later 、Reference example After drying the methacrylic resin compositions obtained in the examples and comparative examples at 80°C for 24 hours, the injection molding machine and the mold for measurement described below were used under the following molding conditions to evaluate the presence or absence of silver streaks. Specifically, the resin was injected into the center of the mold surface under the following conditions, and a spiral molded product was taken out 40 seconds after the injection was completed, and the presence or absence of silver streaks was evaluated. After switching the resin, 20 shots were discarded, and the evaluation was carried out using 50 from the 21st shot to the 70th shot. · Injection molding machine: EC-100SX (manufactured by Toshiba Machine Co., Ltd.) · Mold for measurement: A mold with a groove having a depth of 2 mm and a width of 12.7 mm dug in an Archimedes spiral shape from the center of the surface on the surface of the mold · Molding conditions Resin temperature: 290°C Mold temperature: 70°C Maximum injection pressure: 75 MPa Injection time: 20 sec · Evaluation of the presence or absence of silver streaks ◎: Among 50 samples, the number of samples with silver streaks is 2 or less ○: Among 50 samples, the number of samples with silver streaks is 5 or less △: Among 50 samples, the number of samples with silver streaks is 10 or less ×: Among 50 samples, the number of samples with silver streaks exceeds 10

[0155] <III-5. Evaluation of mold release property> The methacrylic resin compositions obtained in the following Examples 、Reference example and Comparative Examples were dried at 80 °C for 24 hours, and then the injection molding machine and the mold for measurement described below were used under the following molding conditions to evaluate the mold release property Specifically, after switching the resin, 15 shots were discarded, and the evaluation was carried out using 30 shots from the 16th shot to the 45th shot · Injection molding machine: EC-100SX (manufactured by Toshiba Machine Co., Ltd.) · Mold for measurement: Long optical path test piece mold with a thickness of 3 mm × width of 20 mm × length of 220 mm · Molding conditions Resin temperature: 280 °C Mold temperature: 70 °C · Evaluation of mold release property ◎: Among 30 samples, the number of samples with poor mold release is 1 or less ○: Among 30 samples, the number of samples with poor mold release is 3 or less △: Among 30 samples, the number of samples with poor mold release is 7 or less ×: Among 30 samples, the number of samples with poor mold release exceeds 10

[0156] <III-6. Evaluation of weather resistance (resistance to damp heat), measurement of weather resistance (color difference (ΔE*))> As an index for weather resistance evaluation, the color difference (ΔE*) of the sample before and after the exposure test was measured Using the 3-mm-thick test piece formed in (III-5) above, an exposure test was conducted using the method of JIS K7350-4. The exposure conditions were such that the temperature setting of the black panel was 63 ± 3°C, the water spray time setting was (18 ± 0.5) minutes, the spray stop time setting was (102 ± 0.5) minutes, and the total exposure time was 2,040 hours. The test piece was set up such that the 20 mm × 220 mm surface of the previously mentioned 3-mm-thick test piece was the exposed surface. After exposure, the test piece was washed with water, and then its object color was measured. As the color difference, the value of ΔE* was used. The measurement was carried out in accordance with JIS Z8730, using a color difference meter, on the exposed surface of the above-mentioned flat plate-shaped evaluation sample. Specifically, the color difference ΔE* of the transmitted light in the thickness direction from the exposed surface was measured. <Weather resistance evaluation> In the above evaluation, those with ΔE* of 2 or less were rated as "◎" (particularly excellent), those exceeding 2 and less than 2.5 were rated as "○" (good), those from 2.5 to less than 3 were rated as "△" (no practical problems), those from 3 to less than 3.5 were rated as "×" (poor), and those of 3.5 or more were rated as "××" (inferior).

[0157] <III-7. Pressure resistance test> By the same molding as in (III-5) above, a test piece with a thickness of 20 mm × width of 20 mm × length of 120 mm was produced. A hole with a diameter of 5 mm was drilled in the center of the 20 mm × 20 mm part of this test piece, and this hole was extended in the longitudinal direction to penetrate the test piece. Then, the test piece was set on a compressor (manufactured by Hitachi, Ltd., small compressor, 2.2P) so that pressure was applied to the hole part. The operation of applying pressure to the perforated test piece under the condition of 1 Mpa × 1 second was repeated, and the degree of damage to the test piece was observed. <Pressure resistance evaluation> ◎: Even when a pressure load of more than 80,000 times was applied, no damage occurred to the test piece. 〇: When a pressure load of more than 50,000 times and up to 80,000 times was applied, damage occurred to the test piece. △: When a pressure load of more than 30,000 times and up to 50,000 times was applied, damage occurred to the test piece. ×: When a pressure load of 30,000 times or less was applied, the test piece was damaged.

[0158] <IV. Comprehensive Evaluation> In the above evaluation, those with particularly small changes in formability, weather resistance, and the degree of change in YI difference (ΔYI) between long-term retention molding and normal molding are judged to be "5", which are most suitable for industrial equipment and in-vehicle member applications; those judged to be suitable for industrial equipment and in-vehicle member applications are "4"; those judged to be suitable for applications where low heat resistance is not a problem and applications where color change during heating and retention is not a concern are "3"; those judged to be suitable for applications that do not emphasize pressure resistance such as industrial equipment are "2"; those with any defect, poor molding processability, and judged to be not suitable for industrial equipment and in-vehicle member applications are "1".

[0159] Hereinafter, production examples of methacrylic resins will be described.

[0160] 〔Production Example 1〕 Into a container equipped with a stirrer with 4 inclined paddle blades, 2 kg of water, 65 g of tricalcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate were added to obtain a mixed solution (a). Next, 26 kg of water was added to a 60 L reactor equipped with a stirrer with 3 retreat blades and heated to 75 °C. The mixed solution (a) was added, and then 22 kg of a monomer mixed solution prepared by previously mixing 95 parts by mass of methyl methacrylate (A), 5 parts by mass of cyclohexyl maleimide (B-2), 0.295 parts by mass of a chain transfer agent n-octyl mercaptan, and 0.25 parts by mass of a polymerization initiator t-butyl peroxy-2-ethylhexanoate was added. Suspension polymerization was carried out while maintaining at about 75 °C. An exothermic peak was observed about 120 minutes after the raw material mixture was added. Then, after heating to 97 °C at a rate of 1 °C / min, it was aged for 120 minutes, and the polymerization reaction was substantially completed. Next, it was cooled to 50 °C and 20% by mass sulfuric acid was added to dissolve the suspending agent. Next, the polymerization reaction solution was sieved through a 1.68 mm mesh sieve to remove aggregates, and then the water was filtered off. The resulting slurry was dehydrated to obtain a bead-like polymer. The resulting bead-like polymer was washed with water, dehydrated in the same manner as above, and further washed with ion-exchanged water and dehydrated repeatedly to obtain polymer particles. The average particle size was 0.29 mm. The obtained polymer particles were subjected to a devolatilization treatment at 200 rpm and 12 kg / h (resin equivalent) using a 3-vent φ37 mm extruder with a cylinder temperature of 270°C near the die, 260°C in the kneading section, and 230°C from the resin inlet to the kneading section, while adding purified water in an amount of 4% by mass of the resin amount between the resin inlet and the kneading section, to obtain resin pellets. The weight-average molecular weight of the obtained resin pellets was 100,000, and the resin composition determined by NMR was: MMA unit: 95% by mass, CMI unit: 5% by mass.

[0161] [Production Example 2] Into a vessel equipped with a stirrer equipped with four inclined paddle blades were added 2 kg of water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid (a). Next, 26 kg of water was charged into a 60 L reactor equipped with an agitator equipped with three swept-back blades, and the temperature was raised to 75°C. The mixed liquid (a) was then charged, followed by 90 parts by mass of methyl methacrylate (A), 5 parts by mass of cyclohexylmaleimide (B-2), 5 parts by mass of styrene, 0.24 parts by mass of the chain transfer agent n-octyl mercaptan, 0.20 parts by mass of the polymerization initiator t-butylperoxy-2-ethylhexanoate, and 22 kg of a premixed monomer mixed liquid. Suspension polymerization was carried out while maintaining the temperature at about 75°C, and an exothermic peak was observed about 120 minutes after the raw material mixture was added. Thereafter, the temperature was raised to 93° C. at a rate of 1° C. / min, and the mixture was aged for 120 minutes to essentially complete the polymerization reaction. Next, the mixture was cooled to 50° C., and 20% by mass of sulfuric acid was added to dissolve the suspending agent. Next, the polymerization reaction solution was passed through a 1.68 mm mesh sieve to remove aggregates, and then the water was filtered off. The resulting slurry was dehydrated to obtain a bead-like polymer. The resulting bead-like polymer was washed with water and then dehydrated in the same manner as above, and further washed with ion-exchanged water and dehydrated repeatedly to obtain polymer particles. The obtained polymer particles were subjected to a devolatilization treatment at 200 rpm and 12 kg / h (resin equivalent) using a 3-vent φ37 mm extruder with a cylinder temperature of 270°C near the die, 260°C in the kneading section, and 230°C from the resin inlet to the kneading section, while adding purified water in an amount of 4% by mass of the resin amount between the resin inlet and the kneading section, to obtain resin pellets. The weight-average molecular weight of the obtained resin pellets was 110,000, and the resin composition determined by NMR was as follows: MMA unit: 90% by mass, CMI unit: 5% by mass, and St unit: 5% by mass.

[0162] [Production Example 3] Into a vessel equipped with a stirrer equipped with four inclined paddle blades were added 2 kg of water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid (a). Next, 26 kg of water was charged into a 60 L reactor equipped with an agitator equipped with three swept-back blades, and the temperature was raised to 75°C. The mixed liquid (a) was then charged, followed by 89 parts by mass of methyl methacrylate (A), 11 parts by mass of cyclohexylmaleimide (B-2), 5 parts by mass of meta-xylene, 0.208 parts by mass of the chain transfer agent n-octyl mercaptan, 0.25 parts by mass of the polymerization initiator t-butylperoxy-2-ethylhexanoate, and 22 kg of a premixed monomer mixed liquid. Suspension polymerization was carried out at a temperature of about 75°C, and the heat peak occurred about 120 minutes after the raw material mixture was added. A crack was observed. After that, the temperature was raised to 93°C at a rate of 1°C / min, and the mixture was aged for 120 minutes to carry out the polymerization reaction. The question has ended. Next, the mixture was cooled to 50° C., and 20% by mass of sulfuric acid was added to dissolve the suspending agent. Next, the polymerization reaction solution was sieved through a 1.68 mm mesh sieve to remove aggregates, and then the water was filtered off. The resulting slurry was dehydrated to obtain a bead-like polymer. The resulting bead-like polymer was washed with water, dehydrated in the same manner as above, and further washed with ion-exchanged water and dehydrated repeatedly to obtain polymer particles. The average particle size was 0.29 mm. The obtained polymer particles were subjected to a devolatilization treatment at 200 rpm and 12 kg / h (resin equivalent) using a 3-vent φ37 mm extruder with a cylinder temperature of 270°C near the die, 260°C in the kneading section, and 230°C from the resin inlet to the kneading section, while adding purified water in an amount of 4% by mass of the resin amount between the resin inlet and the kneading section, to obtain resin pellets. The weight-average molecular weight of the obtained resin pellets was 130,000, and the resin composition determined by NMR was: MMA unit: 90% by mass, CMI unit: 10% by mass.

[0163] [Production Example 4] A 1.25m stirrer equipped with a paddle blade, a temperature sensor, a cooling tube, and a nitrogen inlet tube was installed. 3 Into the reaction vessel, 470 kg of methyl methacrylate (MMA), 39 kg of N-phenylmaleimide (B-1), 41 kg of N-cyclohexylmaleimide (B-2), 450.0 kg of meta-xylene, and n-octyl mercaptan were charged at 1200 mass ppm relative to 100 mass parts of the total amount of all monomers, and dissolved to prepare a raw material solution. The temperature was raised to 125°C while stirring and passing nitrogen through the solution. Separately, an initiator feed solution was prepared by mixing 0.23 kg of Perhexa C-75 and 1.82 kg of meta-xylene. When the raw material solution reached 127° C., feeding (addition) of the initiator feed liquid (polymerization initiator mixed liquid) was started according to the profiles (1) to (6). (1) 0.0 to 0.5 hours: Feed rate 1.00 kg / hour (2) 0.5 to 1.0 hours: Feed rate 0.50 kg / hour (3) 1.0 to 2.0 hours: Feed rate 0.41 kg / hour (4) 2.0 to 3.0 hours: Feed rate 0.36 kg / hour (5) 3.0 to 4.0 hours: Feed rate 0.14 kg / hour (6) 4.0 to 7.0 hours: Feed rate 0.13 kg / hour After the initiator was fed over a total of 7 hours (B time=7 hours), the reaction was continued for another 2 hours, and the polymerization reaction was carried out for 8 hours from the start of the addition of the initiator. During the polymerization reaction, the internal temperature was controlled at 127±2° C. The polymerization conversion of the obtained polymerization liquid was measured, and the results were as follows: MMA unit: 94.1% by mass, PMI unit: 95.5% by mass, and CMI unit: 93.2% by mass. Overall, the polymerization conversion was 93%. This polymer solution was fed to a concentration device consisting of a tubular heat exchanger and a vaporization tank that had been preheated to 170° C., and the concentration of the polymer contained in the solution was increased to 70% by mass. The resulting polymerized solution was poured into a container with a heat transfer area of ​​0.2 m 2 The polymer was fed to a thin-film evaporator and devolatilized at an internal temperature of 275° C., a feed rate of 25 L / h, a rotation speed of 300 rpm, and a vacuum of 25 Torr. The polymer after devolatilization was pressurized with a gear pump and extruded from a strand die, cooled with water, and cut into resin pellets. The weight average molecular weight of the obtained resin pellets was 120,000, and the resin composition determined by NMR was as follows: MMA unit: 86 mass %, PMI unit: 7 mass %, CMI unit: 7 mass %.

[0164] [Production Example 5] Into a vessel equipped with a stirrer equipped with four inclined paddle blades were added 2 kg of water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid (a). Next, 26 kg of water was charged into a 60 L reactor equipped with an agitator equipped with three swept-back blades, and the temperature was raised to 75°C. Then, the mixed liquid (a) was charged, followed by 22 kg of a monomer mixed liquid prepared in advance by mixing 95 parts by mass of methyl methacrylate (A), 5 parts by mass of cyclohexylmaleimide (B-2), 0.389 parts by mass of the chain transfer agent n-octyl mercaptan, and 0.25 parts by mass of the polymerization initiator t-butylperoxy-2-ethylhexanoate. Suspension polymerization was carried out while maintaining the temperature at about 75°C, and an exothermic peak was observed about 120 minutes after the raw material mixture was added. Thereafter, the temperature was raised to 97° C. at a rate of 1° C. / min, and the mixture was aged for 120 minutes to essentially complete the polymerization reaction. Next, the mixture was cooled to 50° C., and 20% by mass of sulfuric acid was added to dissolve the suspending agent. Next, the polymerization reaction solution was sieved through a 1.68 mm mesh sieve to remove aggregates, and then the water was filtered off. The resulting slurry was dehydrated to obtain a bead-like polymer. The resulting bead-like polymer was washed with water, dehydrated in the same manner as above, and further washed with ion-exchanged water and dehydrated repeatedly to obtain polymer particles. The average particle size was 0.29 mm. The obtained polymer particles were subjected to a devolatilization treatment at 200 rpm and 10 kg / h (resin equivalent) using a three-vent φ37 mm extruder with a cylinder temperature of 250°C near the die, 240°C in the kneading section, and 220°C from the resin inlet to the kneading section, while adding purified water in an amount of 3% by mass of the resin between the resin inlet and the kneading section, to obtain resin pellets. The weight average molecular weight of the obtained resin pellets was 60,000, and the resin composition determined by NMR was: MMA unit: 95% by mass, CMI unit: 5% by mass.

[0165] [Production Example 6] A 200L reactor equipped with a paddle-equipped stirring device, a temperature sensor, a cooling tube, and a nitrogen inlet tube was charged with 69.1 kg of methyl methacrylate (MMA), 5.32 kg of styrene (St), 9.57 kg of methacrylic acid (MAA), 56.0 kg of meta-xylene, and 0.105 kg of n-octyl mercaptan to prepare a raw material solution. The temperature was raised to 117°C while stirring and passing nitrogen through the solution. Separately, an initiator feed liquid A was prepared by mixing 0.029 kg of Perhexa 25B and 0.10 kg of meta-xylene, and an initiator feed liquid B was prepared by mixing 0.0098 kg of Perhexa 25B and 0.10 kg of meta-xylene. When the temperature of the raw material solution reached 117°C, initiator feed liquid A was fed at a feed rate of 0.774 kg / hour for 10 minutes and reacted for 2 hours. Thereafter, initiator feed liquid B was fed at a feed rate of 0.110 kg / hour for 10 minutes and the reaction was continued for another 10 hours, and the polymerization reaction was carried out for a total of 12 hours and 20 minutes to complete the reaction. The obtained polymerization liquid was fed into a high-temperature vacuum chamber set at 280° C., where unreacted materials and the solvent were removed to produce a six-membered cyclic acid anhydride. Composition analysis of the produced copolymer by NMR showed that the copolymer consisted of 78% by mass of MMA units, 7% by mass of St units, 3% by mass of MAA units, and 12% by mass of 6-membered cyclic acid anhydride units. 0.5 kg of the copolymer pellets thus obtained was placed in an autoclave with an internal volume of 5 L, and then 3.0 kg of N,N-dimethylformamide was added and dissolved by stirring. 28% ammonia water containing 2 equivalents of ammonia per unit amount of 6-membered cyclic acid anhydride was added, and the mixture was reacted at 150°C for 2 hours. The reaction solution was extracted and poured into n-hexane to precipitate a polymer, which was then further treated in a 10 torr volatilization furnace at 250° C. for 2 hours. The copolymer finally obtained was pale yellow and transparent, and its composition was determined by nitrogen content determination by elemental analysis, NMR, and IR: MMA unit: 78% by mass, St unit: 7% by mass, MAA unit: 3% by mass, and glutarimide structural unit: 12% by mass. The weight-average molecular weight of the copolymer was 130,000. The above procedure was repeated to prepare the polymers required for evaluation.

[0166] [Production Example 7] Into a vessel equipped with a stirrer equipped with four inclined paddle blades were added 2 kg of water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid (a). Next, 26 kg of water was charged into a 60 L reactor equipped with an agitator equipped with three swept-back blades, and the temperature was raised to 75°C. Then, the mixed liquid (a) was charged, followed by 22 kg of a monomer mixed liquid prepared in advance by mixing 96.5 parts by mass of methyl methacrylate (A), 3.5 parts by mass of methyl acrylate (C-3), 0.28 parts by mass of the chain transfer agent n-octyl mercaptan, and 0.25 parts by mass of the polymerization initiator t-butyl peroxy-2-ethylhexanoate. Suspension polymerization was carried out while maintaining the temperature at about 80°C, and an exothermic peak was observed about 120 minutes after the raw material mixture was added. Thereafter, the temperature was raised to 97° C. at a rate of 1° C. / min, and the mixture was aged for 120 minutes to essentially complete the polymerization reaction. Next, the mixture was cooled to 50° C., and 20% by mass of sulfuric acid was added to dissolve the suspending agent. Next, the polymerization reaction solution was sieved through a 1.68 mm mesh sieve to remove aggregates, and then the water was filtered off. The resulting slurry was dehydrated to obtain a bead-like polymer. The resulting bead-like polymer was washed with water, dehydrated in the same manner as above, and further washed with ion-exchanged water and dehydrated repeatedly to obtain polymer particles. The average particle size was 0.30 mm. The obtained polymer particles were extruded at 200 rpm and 10 kg / h (resin equivalent) while devolatilizing using a 3-vent φ37 mm extruder with the cylinder temperature set to 240°C near the die, 240°C in the kneading section, and 220°C from the resin input to the kneading section. The extruded strands were water-cooled and cut to obtain resin pellets. The weight-average molecular weight of the obtained resin pellets was 100,000, and the resin composition determined by NMR was: MMA unit: 96.5% by mass, methyl acrylate unit: 3.5% by mass.

[0167] Below are examples of methacrylic resin compositions. 、Reference example Also, comparative examples will be described.

[0168] Example 1 100 parts by mass of the resin obtained in the above-mentioned Production Example 1 were blended by hand blending with 0.04 parts by mass of (D-1), 0.03 parts by mass of Tinuvin P, 0.05 parts by mass of Adeka STAB AD2112, and 0.1 parts by mass of Adeka STAB AO-80, and melt-kneaded at a discharge rate of 12 kg / hour, a water bath temperature of 60°C (water contact distance of about 20 cm), and a rotation speed of 180 rpm using a vented (3 places) Φ26 mm twin-screw extruder TEM-26SS (L / D = 48, using a 4-hole die, die setting temperature 250 ° C, barrel setting temperature 250 ° C; outlet side, hopper side barrel setting temperature 220 ° C) manufactured by Toshiba Machine Co., Ltd., to produce a pellet-shaped methacrylic resin composition. The weight average molecular weight of the obtained methacrylic resin composition was 100,000. The resin composition determined by NMR was found to have a MMA unit: 95% by mass, and a CMI unit: 5% by mass. The amount of remaining methyl methacrylate was 1200 ppm by mass relative to 100 parts by mass of the methacrylic resin composition, and the amount of remaining N-cyclohexylmaleimide was 600 ppm by mass relative to 100 parts by mass of the methacrylic resin composition. The above physical property evaluations were carried out using the obtained methacrylic resin composition pellets. The evaluation results are shown in Table 1. A 4 mm thick test piece was prepared using the resin composition pellets obtained in Example 1, and the Charpy impact strength (unnotched) of the 4 mm thick test piece was measured in accordance with the ISO179 / 1eU standard. The result was 16 kJ / m 2 It was. Furthermore, using the resin composition pellets obtained in Example 1, an oil level gauge was produced with external dimensions of 20 mm thickness × 20 mm height × 150 mm width, vertical holes of 12 mm diameter × 20 mm depth (vertical length) (located at two horizontal ends and penetrating vertically), and horizontal holes of 6 mm diameter × 80 mm depth (horizontal length) (located between the two vertical holes, extending horizontally and penetrating the two vertical holes).

[0169] [Example 2~ 9〕、〔Reference Example 10], [Comparative Examples 1 to 3] Methacrylic resin compositions were produced in the same manner as in Example 1 except that the conditions shown in Table 1 were used, and evaluations were carried out. The evaluation results are shown in Table 1.

[0170] Comparative Example 4 The evaluation was carried out using a cast plate of PMMA (Mw: 1 million). The cast plate had high strength but poor fluidity due to its large molecular weight, and was therefore unsuitable for injection molding. The evaluation results are shown in Table 1.

[0171] Comparative Example 5 LC1500 was used as the polycarbonate resin. The evaluation results are shown in Table 1.

[0172] [Table 1]

[0173] As shown in Table 1, when the weight-average molecular weight of the methacrylic resin is within a specified range, the content of component (D) is within a specified range, and the mass ratio (B) / (D) is within a specified range, it was found that the oil level gauge has sufficient optical properties and is excellent in heat resistance, thermal stability, appearance, weather resistance, and moldability. refer to In Example 10, the heat resistance was at a practically sufficient level, but was lower than that of the other Examples. [Industrial Applicability]

[0174] INDUSTRIAL APPLICABILITY The methacrylic resin composition of the present invention and a molded article containing the same have industrial applicability as an oil level gauge.

Claims

1. The present invention includes a methacrylic resin composition, the change rate (ΔYI) of which is 20 or less when the 220 mm long optical path YI value (220 mm long optical path YI value (45 seconds)) measured in accordance with JIS K 7105 for a test piece prepared at an injection molding temperature of 280° C. and a cycle time of 270 seconds is used for a test piece having a thickness of 3 mm, a width of 20 mm, and a length of 220 mm and prepared at an injection molding temperature of 280° C. and a cycle time of 45 seconds is used for a test piece, the change rate (ΔYI) of which is 20 or less when the 220 mm long optical path YI value (220 mm long optical path YI value (270 seconds)) measured in accordance with JIS K 7105 for a test piece prepared at an injection molding temperature of 280° C. and a cycle time of 270 seconds is used for a test piece The methacrylic resin composition contains a methacrylic resin containing 50 to 97% by mass of a methacrylic acid ester monomer unit (A), 3 to 30% by mass of a structural unit (B) having a ring structure in the main chain, and 0 to 20% by mass of another vinyl monomer unit (C) copolymerizable with the methacrylic acid ester monomer. An oil level gauge comprising: ΔYI={220 mm long optical path YI value (270 seconds)−220 mm long optical path YI value (45 seconds)} / 220 mm long optical path YI value (45 seconds) (I)

2. 2. The oil level gauge according to claim 1, wherein the color difference ΔE* measured according to JIS Z8730 before and after a 2040-hour exposure test using a 3 mm thick test piece using the method of JIS K7350-4 is 3 or less.

3. The oil level gauge according to claim 1 or 2, wherein the methacrylic resin composition contains: 100 parts by mass of a methacrylic resin including a structural unit (B) having a ring structure in its main chain; and 0.001 to 0.2 parts by mass of a compound (D) represented by the following general formula (1) or (2): 【Chemistry 1】 (In formula (1), R represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 12 carbon atoms, or an aromatic hydrocarbon group having 6 to 12 carbon atoms. The aliphatic hydrocarbon group and aromatic hydrocarbon group of R may each have a sulfur atom, a nitrogen atom, an oxygen atom, or a phosphorus atom on a carbon atom. Furthermore, R' represents an aliphatic hydrocarbon group having 1 to 12 carbon atoms, or an aromatic hydrocarbon group having 6 to 18 carbon atoms. The aliphatic hydrocarbon group and aromatic hydrocarbon group of R' may each have a sulfur atom, a nitrogen atom, an oxygen atom, or a phosphorus atom on a carbon atom.) 【Chemistry 2】 (In formula (2), R, R', and R'' each independently represent a hydrogen atom, an aliphatic hydrocarbon group having 1 to 12 carbon atoms, or an aromatic hydrocarbon group having 6 to 12 carbon atoms. The aliphatic hydrocarbon group and aromatic hydrocarbon group of R, R', and R'' may each have a sulfur atom, a nitrogen atom, an oxygen atom, or a phosphorus atom on a carbon atom. In addition, R' and R'' may be bonded to each other to form a ring.)

4. 4. The oil level gauge according to claim 3, wherein a ratio ((B) / (D)) of a content of the structural unit (B) having a ring structure in the main chain in the methacrylic resin composition to a content of the component (D) in the methacrylic resin composition is 25 or more and 1,000 or less.

5. The oil level gauge according to claim 2 or 3, wherein the methacrylic resin composition has a weight average molecular weight of 65,000 to 300,000 as measured by gel permeation chromatography (GPC).

6. The oil level gauge according to any one of claims 1 to 5, wherein the structural unit (B) having a ring structure in the main chain includes at least one structural unit selected from the group consisting of a maleimide-based structural unit (B-1), a glutaric anhydride-based structural unit (B-2), a glutarimide-based structural unit (B-3), a lactone ring structural unit (B-4), and an acid anhydride structural unit (B-5).

7. The oil level gauge according to any one of claims 1 to 6, having a thickness of 0.01 to 30 mm.

Citation Information

Patent Citations

  • Transparent heat-resistant resin and method for producing the same

    JP2002060424A

  • Vehicle member including methacryl resin

    JP2014024361A

  • Acrylic rubber

    JP2015081304A

  • Optical member containing methacrylic copolymer resin

    JP2016210963A

  • Methacrylic resin, methacrylic resin composition, film, and production methods

    JP2017101225A